Curable composition, film formation method and manufacturing method of article
By using a hardened composition of a specific composition, bubble problems and overflow adhesion problems during droplet bonding are solved, and printing efficiency and substrate quality are improved.
Patent Information
- Application Number
- JP2023119299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
In the prior printing technology, liquid droplets tend to generate air bubbles when combined on the substrate, resulting in inefficient production, and the hardened composition may spill out of the desired area or adhere to the side walls, causing substrate defects.
A hardening composition containing polymer compounds, photopolymerization initiators and solvents is employed to control its viscosity and surface tension, allowing droplets to quickly bind on the substrate and form a continuous film while reducing spillage and adhesion using surfactants.
The production efficiency of the printing process is improved, bubble formation and overflow of hardening compositions is reduced, and the substrate defect rate is reduced.
Smart Images

Figure 2025016184000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable composition, a film-forming method, and a method for producing an article. [Background technology]
[0002] In semiconductor devices, MEMS, and the like, the demand for miniaturization is increasing, and imprinting technology (photoimprinting technology) has attracted attention as a microfabrication technology. In imprinting technology, a mold having a fine concave-convex pattern formed on its surface is brought into contact with a curable composition supplied (applied) onto a substrate, and the curable composition is cured in that state. In this way, the pattern of the mold is transferred to a cured film of the curable composition, and a pattern is formed on the substrate. With imprinting technology, a fine pattern (structure) on the order of several nanometers can be formed on the substrate.
[0003] An example of a pattern formation method using the imprint technique will be described. First, a liquid curable material is dropped (placed) discretely in a pattern formation region on a substrate. The droplets of the curable composition placed in the pattern formation region spread on the substrate. This phenomenon is called press spreading. Next, a mold is brought into contact (pressed) with the curable composition on the substrate. As a result, the droplets of the curable composition spread over the entire gap between the substrate and the mold by capillary action. This phenomenon is called spreading. The curable composition is filled into the recesses constituting the pattern of the mold by capillary action. This phenomenon is called filling. The time until spreading and filling are completed is called filling time. When filling of the curable composition is completed, the curable composition is irradiated with light to cure the curable composition. Then, the mold is separated from the cured curable composition on the substrate. By carrying out these steps, the pattern of the mold is transferred to the curable composition on the substrate, and a pattern of the curable composition is formed. Here, the pattern of the curable composition formed on the substrate includes a residual film. The residual film is a cured film remaining between the concave portions (convex portions of the mold pattern) of the cured film of the curable composition and the substrate.
[0004] In addition, in the photolithography process for manufacturing semiconductor devices, it is also necessary to planarize the substrate. For example, in extreme ultraviolet exposure technology (EUV), which is a photolithography technology that has been attracting attention in recent years, the focal depth at which a projected image is formed becomes shallow as the size is reduced, so the unevenness of the surface of the substrate to which the curable composition is applied must be suppressed to several tens of nm or less. In the imprint technology, flatness to the same extent as that of EUV is required to improve the filling property and line width accuracy of the curable composition. As a flattening technology, a technology is known in which droplets of a curable composition in an amount corresponding to the unevenness are discretely dropped onto a substrate having unevenness, and the curable composition is cured in a state where a mold having a flat surface is brought into contact with the substrate to obtain a flat surface.
[0005] In a pattern forming method or flattening technique using an imprint technique, droplets of a curable composition dropped onto a substrate are brought into contact with a mold in a state where they are not in contact with each other, so air bubbles are inevitably trapped between the mold, the substrate, and the curable composition. Therefore, it takes a long time for such air bubbles to diffuse into the mold or the substrate and disappear, which is one of the factors that reduce productivity (throughput). Therefore, a technique has been proposed in which droplets of the curable composition are bonded together before the curable composition on the substrate is brought into contact with the mold (see Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2022-188736 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the technology disclosed in Patent Document 1, the droplets of the curable composition dropped onto the substrate spread at such a high speed that the droplets join together, and the curable composition may overflow from the desired region (pattern formation region). The length by which the curable composition overflows from the desired region is called the "overflow amount."
[0008] In the technique disclosed in Patent Document 1, when the mold is brought into contact with the curable composition on the substrate, the curable composition has fluidity, so the curable composition may overflow from the contact surface of the mold and adhere (creep up) to the side wall (side surface) of the mold. This phenomenon in which the curable composition creeps up and adheres to the side wall of the mold is called "seepage." The cured product of the curable composition that adheres to the side wall of the mold remains on the substrate as unwanted matter or falls from the side wall of the mold onto the substrate at an unintended timing, which can cause major defects on the substrate.
[0009] The present invention has been made in consideration of such problems in the conventional technology, and an exemplary object of the present invention is to provide a new technology relating to a curable composition. [Means for solving the problem]
[0010] In order to achieve the above object, one aspect of the present invention provides a curable composition comprising a polymerizable compound (a), a photopolymerization initiator (b), a solvent (d), and a surfactant (c1), wherein the curable composition has a viscosity of 1.3 mPa·s to 60 mPa·s at 23°C and 1 atmospheric pressure, a content of the solvent (d) in the entire curable composition is more than 5 vol% and less than 95 vol%, and the boiling point of the solvent (d) is less than 250°C at 1 atmospheric pressure, and wherein when a contact angle of a composition obtained by excluding the solvent (d) and the surfactant (c1) from the curable composition to a substrate is α1 [°] and a contact angle of a composition obtained by excluding the solvent (d) from the curable composition to the substrate is α2 [°], α2 is greater than α1.
[0011] Further objects or other aspects of the present invention will become apparent from the following description of the embodiments with reference to the accompanying drawings. Effect of the Invention
[0012] According to the present invention, for example, a new technique relating to a curable composition can be provided. [Brief description of the drawings]
[0013] [Figure 1] 1A to 1C are diagrams illustrating a pattern forming method (film forming method) according to one aspect of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining the behavior of droplets of a curable composition after being dropped. [Diagram 3] 1A and 1B are diagrams illustrating the shape of a droplet when a droplet flow is induced by the Marangoni effect. [Figure 4] FIG. 2 is a diagram for explaining the behavior of droplets of a curable composition after being dropped. [Diagram 5] FIG. 2 is a diagram for explaining the behavior of droplets of a curable composition after being dropped. [Figure 6] FIG. 2 is a diagram for explaining the behavior of droplets of a curable composition after being dropped. [Figure 7] FIG. 13 is a diagram for explaining the flow behavior of droplets of a curable composition during a waiting step. [Figure 8] FIG. 2 is a diagram showing a comparison between the contacting process in the prior art and the contacting process in the present invention. [Figure 9] FIG. 1 is a diagram for explaining the concept of the seepage phenomenon. [Figure 10] FIG. 2 is a diagram showing the state in which the curable composition has crawled up the side wall of a mold. [Figure 11] FIG. 13 is a diagram showing the results of measuring the contact angle with respect to a substrate. [Figure 12] FIG. 13 is a diagram showing the results of measuring surface tension. [Figure 13] FIG. 13 is a diagram showing the change in radius of a droplet over time. [Figure 14] FIG. 13 is a diagram showing the results of measuring the amount of overflow of a liquid film. [Figure 15] FIG. 13 is a diagram showing a state in which a droplet is isolated on a substrate. [Figure 16] FIG. 2 shows a state in which a substantially continuous liquid film is formed on a substrate. [Figure 17] FIG. 1 shows a summary of experimental results for three compositions. [Figure 18]FIG. 13 shows the dependence of the maximum radius of a droplet on Δγ. [Figure 19] FIG. 13 is a diagram showing the results of measuring the contact angle with respect to a mold. [Figure 20] FIG. 13 is a diagram showing the results of numerical calculation of seepage height. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiments will be described in detail with reference to the attached drawings. Note that the following embodiments do not limit the invention according to the claims. Although the embodiments describe a number of features, not all of these features are essential to the invention, and the features may be combined in any manner. Furthermore, in the attached drawings, the same reference numbers are used for the same or similar configurations, and duplicated descriptions are omitted.
[0015] Means for Solving the Problems In providing a new technology relating to a curable composition, the present inventors have discovered a curable composition and process conditions therefor that enable droplets of the curable composition discretely dropped (arranged) on a substrate to bond to each other and that enable a solvent contained in the curable composition to volatilize.
[0016] [Curable composition] The curable composition (A) in the present invention is a curable composition for inkjet printing. The curable composition (A) in the present invention is a composition containing at least a polymerizable compound (a), a photopolymerization initiator (b), and a solvent (d).
[0017] In addition, in this specification, the cured film means a film obtained by polymerizing and curing a curable composition on a substrate. The shape of the cured film is not particularly limited, and the surface may have a pattern shape. In addition, the cured film remaining between the concave portion (convex portion of the mold pattern) of the cured film of the curable composition and the substrate is called a residual film.
[0018] <Component (a): Polymerizable compound> Component (a) is a polymerizable compound. In this specification, the polymerizable compound is a compound that reacts with a polymerization factor (radical, etc.) generated from a photopolymerization initiator (component (b)) to form a film made of a polymer compound by a chain reaction (polymerization reaction).
[0019] Examples of such polymerizable compounds include radically polymerizable compounds. The polymerizable compound of component (a) may be composed of only one type of polymerizable compound, or may be composed of multiple types (one or more) of polymerizable compounds.
[0020] Examples of the radically polymerizable compound include (meth)acrylic compounds, styrene compounds, vinyl compounds, allyl compounds, fumaric compounds, and maleyl compounds.
[0021] The (meth)acrylic compound is a compound having one or more acryloyl groups or methacryloyl groups. Examples of monofunctional (meth)acrylic compounds having one acryloyl group or one methacryloyl group include, but are not limited to, the following: Phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, EO modified p-cumylphenol (meth)acrylate, 2-bromophenoxyethyl (meth)acrylate, 2,4-dibromophenoxyethyl (meth)acrylate, 2,4,6-tribromophenoxyethyl (meth)acrylate, EO modified phenoxy (meth)acrylate, PO modified phenoxy (meth)acrylate, polyoxyethylene nonylphenyl ether (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate t) acrylate, cyclohexyl (meth)acrylate, 4-butylcyclohexyl (meth)acrylate, acryloylmorpholine, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pliers (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, benzyl (meth)acrylate, Tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, diacetone (meth)acrylamide, isobutoxymethyl (meth)acrylamide, N,N-dimethyl(meth)acrylamide, t-octyl(meth)acrylamide, dimethylaminoethyl(meth)acrylate, diethylaminoethyl(meth)acrylate, 7-amino-3,7-dimethyloctyl(meth)acrylate, N,N-diethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, 1- or 2-naphthyl(meth)acrylate, 1- or 2-naphthylmethyl(meth)acrylate, 3- or 4-phenoxybenzyl(meth)acrylate, chinoabenzyl(meth)acrylate, naphthalenemethyl(meth)acrylate, Examples of commercially available products of the above-mentioned monofunctional (meth)acrylic compounds include, but are not limited to, the following. Aronix (registered trademark) M101, M102, M110, M111, M113, M117, M5700, TO-1317, M120, M150, M156 (all manufactured by Toagosei), MEDOL10, M IBDOL10, CHDOL10, MMDOL30, MEDOL30, MIBDOL30, CHDOL30, LA, IBXA, 2-MTA, HPA, Viscoat #150, #155, #158, #19 0, #192, #193, #220, #2000, #2100, #2150 (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), light acrylate BO-A, EC-A, DMP-A, THF-A, HOP-A, HOA-MPE, HOA-MPL, PO-A, P-200A, NP-4EA, NP-8EA, epoxy ester M-600A, POB-A, OPP-EA (all manufactured by Kyoeisha Chemical Co., Ltd.), KAYARAD (registered trademark) TC110S, R-564, R-128H (all manufactured by Nippon Kayaku), NK Ester AMP-10G, AMP-20G, A-LEN-10 (all manufactured by Shin-Nakamura Chemical Co., Ltd.), FA-511A, 512A, 513A (all manufactured by Hitachi Chemical), PHE, CEA, PHE-2, PHE-4, BR-31, BR-31M, BR-32 (all manufactured by Daiichi Kogyo Seiyaku), VP (manufactured by BASF), ACMO, DMAA, DMAPAA (all manufactured by Kohjin), HRD-01 (all manufactured by Nippon Shokubai) Furthermore, examples of polyfunctional (meth)acrylic compounds having two or more acryloyl groups or methacryloyl groups include, but are not limited to, the following: Trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO modified trimethylolpropane tri(meth)acrylate, PO modified trimethylolpropane tri(meth)acrylate, EO,PO modified trimethylolpropane tri(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1, 9-Nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,3-adamantanedimethanol di(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, tris(acryloyloxy)isocyanurate, bis(hydroxymethyl)tricyclodecane di(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, EO-modified 2,2-bis(4-((meth)acryloxy)phenyl)propane, PO-modified 2,2-bis(4-((meth)acryloxy)phenyl)propane, EO,PO-modified 2,2-bis(4-((meth)acryloxy)phenyl)propane, o-, m- or p-benzenedi(meth)acrylate, o-, m- or p-xylylenedi(meth)acrylate Examples of commercially available products of the above-mentioned polyfunctional (meth)acrylic compounds include, but are not limited to, the following. Upimer (registered trademark) UV SA1002, SA2007 (all manufactured by Mitsubishi Chemical), Viscoat #195, #230, #215, #260, #335HP, #295, #300, #360, #700, GPT, 3PA (all manufactured by Osaka Organic Chemical Industry), Light Acrylate 4EG-A, 9EG-A, NP-A, DCP-A, BP-4EA, BP-4PA, TMP-A, PE-3A, PE-4A, DPE-6A (all manufactured by Kyoeisha Chemical), KAYARAD (registered trademark) PET-30, TMPTA, R-604, DPHA, DPCA-20, -30, -60, -120, HX-620, D-310, D-330 (all manufactured by Nippon Kayaku Co., Ltd.), Aronix (registered trademark) M208, M210, M215, M220, M240, M305, M309, M310, M315, M325, M400 (all manufactured by Toagosei Co., Ltd.), Lipoxy (registered trademark) VR-77, VR-60, VR-90 (all manufactured by Showa Polymer Co., Ltd.), Oxol EA-0200, Oxol EA-0300 (all manufactured by Osaka Gas Chemicals Co., Ltd.), SR295, SR355 (all manufactured by Sartomer Co., Ltd.) In the above-mentioned compound group, (meth)acrylate means acrylate or methacrylate having an alcohol residue equivalent thereto. (Meth)acryloyl group means acryloyl group or methacryloyl group having an alcohol residue equivalent thereto. EO means ethylene oxide, and EO-modified compound A means a compound in which the (meth)acrylic acid residue and the alcohol residue of compound A are bonded via a block structure of an ethylene oxide group. PO means propylene oxide, and PO-modified compound B means a compound in which the (meth)acrylic acid residue and the alcohol residue of compound B are bonded via a block structure of a propylene oxide group.
[0022] Specific examples of styrene-based compounds include, but are not limited to, the following: Alkylstyrenes such as styrene, 2,4-dimethyl-α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 2,6-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, 2,4,6-trimethylstyrene, 2,4,5-trimethylstyrene, pentamethylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, diethylstyrene, triethylstyrene, propylstyrene, 2,4-diisopropylstyrene, butylstyrene, hexylstyrene, heptylstyrene and octylstyrene; fluorostyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, m-bromostyrene, p-bromostyrene, dibromostyrene and iodine. halogenated styrenes such as styrene; compounds having a styryl group as a polymerizable functional group, such as nitrostyrene, acetylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, 2-vinylbiphenyl, 3-vinylbiphenyl, 4-vinylbiphenyl, 1-vinylnaphthalene, 2-vinylnaphthalene, 4-vinyl-p-terphenyl, 1-vinylanthracene, α-methylstyrene, o-isopropenyltoluene, m-isopropenyltoluene, p-isopropenyltoluene, 2,3-dimethyl-α-methylstyrene, 3,5-dimethyl-α-methylstyrene, p-isopropyl-α-methylstyrene, α-ethylstyrene, α-chlorostyrene, divinylbenzene, diisopropylbenzene, and divinylbiphenyl; Specific examples of vinyl compounds include, but are not limited to, the following: Vinylpyridine, vinylpyrrolidone, vinylcarbazole, vinyl acetate and acrylonitrile; conjugated diene monomers such as butadiene, isoprene and chloroprene; vinyl halides such as vinyl chloride and vinyl bromide; vinylidene halides such as vinylidene chloride; vinyl esters of organic carboxylic acids and their derivatives (vinyl acetate, vinyl propionate, vinyl butyrate, vinyl benzoate, divinyl adipate, (meth)acrylonitrile, etc.), compounds having a vinyl group as a polymerizable functional group. In this specification, (meth)acrylonitrile is a general term for acrylonitrile and methacrylonitrile.
[0023] Examples of acrylic compounds include, but are not limited to, the following: Allyl acetate, Allyl benzoate, Diallyl adipate, Diallyl terephthalate, Diallyl isophthalate, Diallyl phthalate Examples of fumarole compounds include, but are not limited to, the following: Dimethyl fumarate, diethyl fumarate, diisopropyl fumarate, di-sec-butyl fumarate, diisobutyl fumarate, di-n-butyl fumarate, di-2-ethylhexyl fumarate, dibenzyl fumarate Examples of maleyl compounds include, but are not limited to, the following: Dimethyl maleate, diethyl maleate, diisopropyl maleate, di-sec-butyl maleate, diisobutyl maleate, di-n-butyl maleate, di-2-ethylhexyl maleate, dibenzyl maleate Examples of other radical polymerizable compounds include, but are not limited to, the following: Dialkyl esters of itaconic acid and their derivatives (dimethyl itaconate, diethyl itaconate, diisopropyl itaconate, di-sec-butyl itaconate, diisobutyl itaconate, di-n-butyl itaconate, di-2-ethylhexyl itaconate, dibenzyl itaconate, etc.), N-vinylamide derivatives of organic carboxylic acids (N-methyl-N-vinylacetamide, etc.), maleimide and its derivatives (N-phenylmaleimide, N-cyclohexylmaleimide, etc.) When component (a) is composed of a plurality of compounds having one or more polymerizable functional groups, it is preferable to include both a monofunctional polymerizable compound and a polyfunctional polymerizable compound. The ratio of the polyfunctional polymerizable compound in component (a) is preferably 20% by weight or more, more preferably 25% by weight or more, and particularly preferably 40% by weight or more. This is because by combining a monofunctional polymerizable compound and a polyfunctional polymerizable compound, a cured film having excellent balance of performance such as high mechanical strength, high dry etching resistance, and high heat resistance can be obtained.
[0024] In the film forming method of the present invention, it takes several milliseconds to several hundred seconds for the droplets of the curable composition (A) arranged discretely on the substrate to combine with each other to form a substantially continuous liquid film, so a waiting step described below is necessary. In the waiting step, the solvent (d) is volatilized while the polymerizable compound (a) must not volatilize. Therefore, the boiling point of each of the one or more polymerizable compounds contained in the polymerizable compound (a) under normal pressure is preferably 250°C or higher, more preferably 300°C or higher, and even more preferably 350°C or higher. In addition, in order to obtain high dry etching resistance and high heat resistance in the cured film of the curable composition (A), it is preferable to contain at least a compound having a ring structure such as an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure. Note that normal pressure is defined as 1 atmosphere (atmospheric pressure).
[0025] The boiling point of the polymerizable compound (a) generally correlates with the molecular weight. Therefore, the molecular weight of each of the one or more polymerizable compounds contained in the polymerizable compound (a) is preferably 200 or more, more preferably 240 or more, and even more preferably 250 or more. However, even if the molecular weight is 200 or less, as long as the boiling point is 250°C or more, it can be preferably used as the polymerizable compound (a) in the present invention. In this way, the boiling point of each of the one or more polymerizable compounds contained in the polymerizable compound (a) under normal pressure is preferably 250°C or more.
[0026] The vapor pressure of the polymerizable compound (component (a)) at 80°C is preferably 0.001 mmHg or less. When the polymerizable compound (a) contains one or more polymerizable compounds, each of the one or more polymerizable compounds may have a vapor pressure of 0.001 mmHg or less at 80°C. This is because, although it is preferable to heat the curable composition in order to accelerate the volatilization of the solvent (component (d)) described later, the volatilization of the polymerizable compound (a) is suppressed during such heating.
[0027] The boiling points and vapor pressures of various organic compounds under normal pressure can be calculated using Hansen Solubility Parameters in Practice (HSPiP) 5th Edition.5.3.04 or the like.
[0028] <Oonishi parameters for component (a)> Dry etching rate of organic compound V, total number of atoms in the organic compound N, total number of carbon atoms in the composition N C , and the total number of oxygen atoms in the composition N O is known to be related by the following formula (1). V∝N / (Nc-No) Equation (1) Here, N / (Nc-No) is also called the "Ohnishi parameter" (hereinafter referred to as "OP"). For example, U.S. Patent Application Publication No. 2020 / 0286740 discloses a technology for obtaining a photocurable composition having high dry etching resistance by using a polymerizable compound component having a small OP.
[0029] According to formula (1), it is suggested that the more oxygen atoms there are in the molecule of an organic compound, or the fewer aromatic ring structures or alicyclic structures there are, the larger the OP is and the faster the dry etching rate is.
[0030] In the curable composition (A) of the present invention, the OP of component (a) is set to 1.80 or more and 4.00 or less. The OP of component (a) is more preferably 2.00 or more and 3.50 or less, and particularly preferably 2.40 or more and 3.00 or less. By setting the OP of component (a) to 4.00 or less, the cured film of the curable composition (A) has high dry etching resistance. In addition, by setting the OP of component (a) to 1.80 or more, it becomes easy to remove the cured film of the curable composition (A) after processing the underlayer using the cured film of the curable composition (A). When component (a) is a mixture of multiple types of polymerizable compounds a1, a2, ..., a n In the case where the component (a) is composed of the above, OP is calculated as a weighted average based on the molar fraction (molar fraction weighted average) as shown in the following formula (2). In this way, when the component (a) contains one or more polymerizable compounds, the OP of the component (a) is calculated by the N / (N C -N O ) values are calculated as the mole fraction weighted average.
[0031]
number
[0032] Here, OP n is component a n The OP of n is component a n is the mole fraction of the entire component (a).
[0033] In order to adjust the OP of component (a) to 1.80 or more and 2.70 or less, it is preferable to include, as at least component (a), a compound (a-1) having two or more cyclic structures, at least one of which is an aromatic structure or an aromatic heterocyclic structure.
[0034] <Compound (a-1): Polymerizable compound having an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure> The polymerizable compound (a) in the present invention may contain a polymerizable compound (a-1) having an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure. Furthermore, the ratio of the component (a-1) in the component (a) is preferably 65% by weight or more. By making the ratio of the component (a-1) 65% by weight or more, it is possible to suppress the OP to 2.70 or less.
[0035] The cyclic structure may be an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure.
[0036] The aromatic structure preferably has a carbon number of 6 to 22, more preferably 6 to 18, and further preferably 6 to 10. Specific examples of the aromatic ring include the following. Benzene ring, naphthalene ring, anthracene ring, phenanthrene ring, phenalene ring, fluorene ring, benzocyclooctene ring, acenaphthylene ring, biphenylene ring, indene ring, indane ring, triphenylene ring, pyrene ring, chrysene ring, perylene ring, tetrahydronaphthalene ring Among the above aromatic rings, a benzene ring or a naphthalene ring is preferred, and a benzene ring is more preferred. The aromatic ring may have a structure in which a plurality of rings are linked together, and examples of the aromatic ring include a biphenyl ring and a bisphenyl ring.
[0037] The aromatic heterocyclic structure preferably has a carbon number of 1 to 12, more preferably 1 to 6, and further preferably 1 to 5. Specific examples of the aromatic heterocyclic ring include the following. A thiophene ring, a furan ring, a pyrrole ring, an imidazole ring, a pyrazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxadiazole ring, an oxazole ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a pyridazine ring, an isoindole ring, an indole ring, an indazole ring, a purine ring, a quinolizine ring, an isoquinoline ring, a quinoline ring, a phthalazine ring, a naphthyridine ring, a quinoxaline ring, a quinazoline ring, a cinnoline ring, a carbazole ring, an acridine ring, a phenazine ring, a phenothiazine ring, a phenoxathiin ring, and a phenoxazine ring. The carbon number of the alicyclic structure is preferably 3 or more, more preferably 4 or more, and even more preferably 6 or more. The carbon number of the alicyclic structure is preferably 22 or less, more preferably 18 or less, even more preferably 6 or less, and even more preferably 5 or less. Specific examples thereof include the following. Cyclopropane ring, cyclobutane ring, cyclobutene ring, cyclopentane ring, cyclohexane ring, cyclohexene ring, cycloheptane ring, cyclooctane ring, dicyclopentadiene ring, spirodecane ring, spirononane ring, tetrahydrodicyclopentadiene ring, octahydronaphthalene ring, decahydronaphthalene ring, hexahydroindane ring, bornane ring, norbornane ring, norbornene ring, isobornane ring, tricyclodecane ring, tetracyclododecane ring, adamantane ring Specific examples of the polymerizable compound (a-1) having a boiling point of 250° C. or higher include, but are not limited to, the following: 3-Phenoxybenzyl acrylate (mPhOBzA, OP 2.54, boiling point 367.4°C, vapor pressure at 80°C 0.0004mmHg, molecular weight 254.3),
[0038] [ka]
[0039] 1-Naphthyl acrylate (NaA, OP 2.27, boiling point 317°C, vapor pressure at 80°C 0.0422mmHg, molecular weight 198),
[0040] [ka]
[0041] 2-Phenylphenoxyethyl acrylate (PhPhOEA, OP2.57, boiling point 364.2℃, vapor pressure at 80℃ 0.0006mmHg, molecular weight 268.3),
[0042] [ka]
[0043] 1-Naphthylmethyl acrylate (Na1MA, OP 2.33, boiling point 342.1℃, vapor pressure at 80℃ 0.042mmHg, molecular weight 212.2),
[0044] [ka]
[0045] 2-Naphthyl methyl acrylate (Na2MA, OP2.33, boiling point 342.1℃, vapor pressure at 80℃ 0.042mmHg, molecular weight 212.2)
[0046] [ka]
[0047] DPhPA (OP2.38, boiling point 354.5℃, vapor pressure 0.0022mmHg at 80℃, molecular weight 266.3) shown in the following formula,
[0048] [ka]
[0049] PhBzA (OP2.29, boiling point 350.4℃, vapor pressure 0.0022mmHg at 80℃, molecular weight 238.3) shown in the following formula,
[0050] [ka]
[0051] FLMA (OP2.20, boiling point 349.3℃, vapor pressure 0.0018mmHg at 80℃, molecular weight 250.3) shown in the following formula,
[0052] [ka]
[0053] ATMA (OP2.13, boiling point 414.9℃, vapor pressure 0.0001mmHg at 80℃, molecular weight 262.3) shown in the following formula,
[0054] [ka]
[0055] DNaMA (OP 2.00, boiling point 489.4℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 338.4) shown in the following formula,
[0056] [ka]
[0057] BPh44DA (OP2.63, boiling point 444℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 322.3) shown in the following formula,
[0058] [ka]
[0059] BPh43DA (OP2.63, boiling point 439.5℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 322.3) shown in the following formula,
[0060] [ka]
[0061] DPhEDA (OP2.63, boiling point 410℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 322.3) shown in the following formula,
[0062] [ka]
[0063] BPMDA (OP 2.68, boiling point 465.7℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 364.4) shown in the following formula,
[0064] [ka]
[0065] Na13MDA (OP 2.71, boiling point 438.8℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 296.3) shown in the following formula,
[0066] [ka]
[0067] The following formula (a-1-1) (OP 2.40, boiling point 333.4℃, vapor pressure at 80℃ 0.0181mmHg, molecular weight 199.2),
[0068] [ka]
[0069] The following formula (a-1-2) (OP 2.40, boiling point 333.4℃, vapor pressure at 80℃ 0.0181mmHg, molecular weight 199.2),
[0070] [ka]
[0071] The following formula (a-1-3) (OP 1.86, boiling point 369.5℃, vapor pressure at 80℃ 0.0053mmHg, molecular weight 193.3),
[0072] [ka]
[0073] The following formula (a-1-4) (OP 2.85, boiling point 438.8℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 296.3),
[0074] [ka]
[0075] The following formula (a-1-5) (OP 2.71, boiling point 438.8℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 296.3),
[0076] [ka]
[0077] The following formula (a-1-6) (OP 2.87, boiling point 421.0℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 338.4),
[0078] [ka]
[0079] The following formula (a-1-7) (OP 2.87, boiling point 465.2℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 338.4),
[0080] [ka]
[0081] The following formula (a-1-8) (OP 2.68, boiling point 465.7℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 364.4),
[0082] [ka]
[0083] The following formula (a-1-9) (OP 2.50, boiling point 433.1℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 320.3),
[0084] [ka]
[0085] The following formula (a-1-10) (OP 2.64, boiling point 468.1℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 326.4),
[0086] [ka]
[0087] The following formula (a-1-11) (OP 3.25, boiling point 553.4℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 358.4),
[0088] [ka]
[0089] The following formula (a-1-12) (OP 2.63, boiling point 443.9℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 322.4),
[0090] [ka]
[0091] The following formula (a-1-13) (OP 2.89, boiling point 509.3℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 406.4),
[0092] [ka]
[0093] The following formula (a-1-14) (OP 2.63, boiling point 450.0℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 322.4),
[0094] [ka]
[0095] The following formula (a-1-15) (OP 3.00, boiling point 476.5℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 366.4)
[0096] [ka]
[0097] The following formula (a-1-16) (OP 2.68, boiling point 447.4℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 364.4)
[0098] [ka]
[0099] The following formula (a-1-17) (OP 2.36, boiling point 543.8℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 398.5),
[0100] [ka]
[0101] The following formula (a-1-18) (OP 3.27, boiling point 526.9℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 396.4),
[0102] [ka]
[0103] The following formula (a-1-19) (OP 2.71, boiling point 333.7℃, vapor pressure 0.0302mmHg at 80℃, molecular weight 244.3),
[0104] [ka]
[0105] The following formula (a-1-20) (OP 2.73, boiling point 333.7℃, vapor pressure at 80℃ 0.0134mmHg, molecular weight 258.3),
[0106] [ka]
[0107] The following formula (a-1-21) (OP 2.71, boiling point 319.2℃, vapor pressure at 80℃ 0.0566mmHg, molecular weight 262.3),
[0108] [ka]
[0109] The following formula (a-1-22) (OP 2.71, boiling point 336.9°C, vapor pressure at 80°C 0.0055mmHg, molecular weight 244.3),
[0110] [ka]
[0111] The following formula (a-1-23) (OP 3.00, boiling point 370.9℃, vapor pressure at 80℃ 0.0021mmHg, molecular weight 274.4),
[0112] [ka]
[0113] The following formula (a-1-24) (OP 3.00, boiling point 376.4℃, vapor pressure at 80℃ 0.0005mmHg, molecular weight 274.4),
[0114] [ka]
[0115] The following formula (a-1-25) (OP 3.00, boiling point 379.4℃, vapor pressure at 80℃ 0.0002mmHg, molecular weight 288.4),
[0116] [ka]
[0117] The following formula (a-1-26) (OP 2.33, boiling point 360.8°C, vapor pressure at 80°C 0.0006mmHg, molecular weight 252.3),
[0118] [ka]
[0119] The following formula (a-1-27) (OP 2.54, boiling point 371.5℃, vapor pressure 0.0003mmHg at 80℃, molecular weight 254.3),
[0120] [ka]
[0121] The following formula (a-1-28) (OP 2.57, boiling point 381.2℃, vapor pressure at 80℃ 0.0001mmHg, molecular weight 268.3),
[0122] [ka]
[0123] The following formula (a-1-29) (OP 2.57, boiling point 381.8℃, vapor pressure at 80℃ 0.0004mmHg, molecular weight 268.3),
[0124] [ka]
[0125] The following formula (a-1-30) (OP 2.50, boiling point 487.4℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 374.4),
[0126] [ka]
[0127] The following formula (a-1-31) (OP 2.67, boiling point 417.2℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 268.3),
[0128] [ka]
[0129] The following formula (a-1-32) (OP 2.67, boiling point 417.2℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 268.3),
[0130] [ka]
[0131] The following formula (a-1-33) (OP 2.67, boiling point 417.2℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 268.3),
[0132] [ka]
[0133] The following formula (a-1-34) (OP 2.67, boiling point 417.2℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 268.3),
[0134] [ka]
[0135] The following formula (a-1-35) (OP 2.71, boiling point 438.8℃, vapor pressure at 80℃ <0.0001mmHg, molecular weight 296.3),
[0136] [ka]
[0137] <Compound (a-2): Polymerizable compound containing at least Si atom> The polymerizable compound (a) in the present invention may contain a polymerizable compound (a-2) containing at least a Si atom. Furthermore, when the polymerizable compound (a) contains the polymerizable compound (a-2), the curable composition (A) in a state in which the solvent (d) has been removed preferably contains 10% by weight or more of Si atoms based on the entire curable composition (A).
[0138] An example of the polymerizable compound (a-2) containing at least a Si atom may be linear or branched. For example, the cyclic siloxane compound may have the structure shown below. The polymerizable functional group in the group Q having a polymerizable functional group may be, for example, a radically polymerizable functional group. Specific examples of the radically polymerizable functional group include a (meth)acrylic group, a (meth)acrylamide group, a vinylbenzene group, an allyl ether group, a vinyl ether group, and a maleimide group. The group Q having a polymerizable functional group may be any group having the above-mentioned polymerizable functional group.
[0139] [ka]
[0140] Other examples of the polymerizable compound (a-2) include a silsesquioxane skeleton as shown in the following chemical formula (I) and a silicone skeleton as shown in the following chemical formula (II). In the chemical formula (I), m+n=8 (8≧m≧1), and R1 is a divalent organic group. In the chemical formula (II), A, B, R2, and R3 are independently an alkyl group, a cycloalkyl group, an alkoxy group, a phenyl group, or a hydroxyl group having 1 to 6 carbon atoms, t is an integer of 1 to 3, and at least one of A and B is a polymerizable functional group.
[0141] [ka]
[0142] [ka]
[0143] The polymerizable functional group in the groups Q, A, and B having a polymerizable functional group may be, for example, a radically polymerizable functional group. Specific examples of the radically polymerizable functional group include (meth)acrylate-based compounds, (meth)acrylamide-based compounds, vinylbenzene-based compounds, allyl ether-based compounds, vinyl ether-based compounds, and maleimide-based compounds. The group Q having a polymerizable functional group may be any group having the above-mentioned polymerizable functional group.
[0144] The silicon-containing (meth)acrylate compound is a compound having one or more acryloyl groups or methacryloyl groups. Examples of monofunctional (meth)acrylate compounds having one silicon-containing acryloyl group or methacryloyl group include, but are not limited to, the following: (2-acryloylethoxy)trimethylsilane, N-(3-acryloyl-2-hydroxypropyl)-3-aminopropyltriethoxysilane, acryloxymethyltrimethoxysilane, (acryloxymethyl)phenethyltrimethoxysilane, acryloxymethyltrimethylsilane, (3-acryloxypropyl)dimethylmethoxysilane, (3-acryloxypropyl)methylbis(trimethylsiloxy)silane, (3-acryloxypropyl)methyldichlorosilane, (3-acryloxypropyl)methyldiethoxysilane, (3-acryloxypropyl)methyldimethoxysilane, (3-acryloxypropyl)trichlorosilane, (3-acryloxypropyl)trimethoxysilane, (3-acryloxypropyl)tris(trimethylsiloxy)silane, acryloxytriisopropylsilane, acryloxytrimethylsilane, methacryloxymethyltrimethoxysilane, 0-(methacryloxyethoxy)carbamoylpropylmethyldimethoxysilane, (methacryloxymethyl)bis(trimethylsiloxy)methylsilane, N-(3-methacryloyl-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (Methacryloxymethyl)methyldimethoxysilane, (Methacryloxymethyl)methyldiethoxysilane, methacryloxymethyltriethoxysilane, methacryloxypropyltrimethoxysilane, Methacryloylpropyltriisopropoxysilane, O-(methacryloxyethyl)-N-(triethoxysilylpropyl)carbamate, methacryloxypropylmethyldimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropyldimethylmethoxysilane, methacryloxypropyldimethylethoxysilane, (Methacryloxymethyl)dimethylethoxysilane, methacryloxypropyltriethoxysilane, methacryloxypropyl silatrane, methacryloxypentamethyldisiloxane, (Methacryloxymethyl)phenyldimethylsilane, methacryloxytrimethylsilane, methacryloxymethyltrimethylsilane, (3-methacryloxy-2-hydroxypropoxypropyl)methylbis(trimethylsiloxy)silane, methacryloxypropyl pentamethyldisiloxane, 0-(methacryloxyethyl)-3-[bis(trimethylsiloxy)methylsilyl]propylcarbamate, methacryloxymethyltris(trimethylsiloxy)silane, methacryloxyethoxytrimethylsilane, (3-methacryloxy-2-hydroxypropoxypropyl)methylbis(trimethylsiloxy)silane, methacryloxypropyltris(vinyldimethylsiloxy)silane, methacryloxypropyltris(trimethylsiloxy)silane, 3-methacryloxypropyltriacetoxysilane, methacryloxypropylmethyldichlorosilane, methacryloxypropyltrichlorosilane, 3-methacrylic acid propyl bis(trimethylsiloxy)methyl silane, 3-Methoxypropyldimethylchlorosilane, 0-Methacryloxy(polyethyleneoxy)trimethylsilane, Poly(methacrylic propyl silsesquioxane), Methacryloxypropylheptaisobutyl-T8-silsesquioxane, Methacryloxypropyltris(trimethylsiloxy)silane Examples of commercially available products of the above-mentioned silicon-containing monofunctional (meth)acrylate compounds include, but are not limited to, the following: SIA0160.0, SIA0180.0, SIA0182.0, SIA0184.0, SIA0186.0, SIA0190.0, SIA0194.0, SIA0196.0, SIA0197.0, SIA0198.0, SIA0199.0, SIA0200.0, SIA0200.A1, SIA0210.0, SIA0315.0, SIA0320.0 , SIM6483.0, SIM6487.5, SIM6480.76, SIM6481.2, SIM6486.1, SIM6481.1, SIM6481.46, SIM6481 .43, SIM6482.0, SIM6487.4, SIM6487.35, SIM6480.8, SIM6486.9, SIM6486.8, SIM6486.5, SIM648 6.4, SIM6481.3, SIM6487.3, SIM6487.1, SIM6487.6, SIM6486.14, SIM6481.48, SIM6481.5, SIM6 491.0, SIM6485.6, SIM6481.15, SIM6487.0, SIM6481.05, SIM6485.8, SIM6481.0, SIM6487.4LI, S IM6481.16, SIM6487.8, SIM6487.6HP, SIM6487.17, SIM6486.7, SIM6487.2, SIM6486.0, SIM6486.2, SIM6487.6-06, SIM6487.6-20, SIM6485.9, SST-R8C42, SLT-3R01, SIM6486.65 (all manufactured by GELEST), TM-0701T, FM-0711, FM-0721, FM-0725 (all manufactured by JNC) The silicon-containing (meth)acrylamide compound is a compound having one or more acrylamide groups or methacrylamide groups. Examples of monofunctional (meth)acrylamide compounds having one silicon-containing acrylamide group or methacrylamide group include, but are not limited to, the following: 3-Acrylamidepropyltrimethoxysilane, 3-Acrylamidepropyltris(trimethylsiloxy)silane Examples of commercially available silicon-containing monofunctional (meth)acrylamide compounds include, but are not limited to, the following: SIA0146.0, SIA0150.0 (both manufactured by GELEST) Furthermore, examples of polyfunctional (meth)acrylate compounds having two or more acryloyl groups or methacryloyl groups include, but are not limited to, the following: A linear polydimethylsiloxane modified at both ends with acryloxypropyl groups, A linear polydimethylsiloxane modified at both ends with methacryloxypropyl groups, A cyclic siloxane modified with multiple acryloxypropyl groups; A cyclic siloxane modified with multiple methacryloxypropyl groups; Silsesquioxane modified with multiple acryloxypropyl groups; Silsesquioxane modified with multiple methacryloxypropyl groups Examples of commercially available products of the above-mentioned silicon-containing polyfunctional (meth)acrylate compounds include, but are not limited to, the following: SIA0200.2, SIA0200.3, SIM6487.42, DMS-R11, DMS-R05, DMS-R22, DMS-R18, DMS-R31 (all manufactured by GELEST), FM-7711, FM-7721, FM-7725 (all manufactured by JNC), X-22-2445 (Shin-Etsu Chemical), AC-SQ TA-100, MAC-SQ TM-100, AC-SQSI-20, MAC-SQ SI-20 (all manufactured by Toagosei) In addition, for example, the following can be synthesized and / or obtained from known document 1. Linear modified polydimethylsiloxane (MA-Si-12) with both ends modified with methacryloxypropyl groups, 8-ring siloxane modified with four methacryloxypropyl groups, 10-ring siloxane modified with five methacryloxypropyl groups, Publicly known literature 1: “Ultraviolet curable branched siloxanes as low-k dielectric for imprint lithography” by Ogawa et al. The blending ratio of component (a) in the curable composition (A) is preferably 40% by weight or more and 99% by weight or less based on the total mass of the synthesis of component (a), component (b) described later, and component (c) described later, i.e., all components excluding the solvent (d). Also, it is more preferably 50% by weight or more and 95% by weight or less, and even more preferably 60% by weight or more and 90% by weight or less. By making the blending ratio of component (a) 40% by weight or more, the mechanical strength of the cured film of the curable composition is increased. Also, by making the blending ratio of component (a) 99% by weight or less, the blending ratio of component (b) or component (c) can be increased, and properties such as a fast photopolymerization rate can be obtained. At least a part of component (a) containing one or more polymerizable compounds may be a polymer having a polymerizable functional group. Such a polymer preferably contains at least a ring structure such as an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure. For example, it is preferable to contain at least one of the constitutional units represented by any of the following structures (1) to (6).
[0145] [ka]
[0146] In the structures (1) to (6), the substituents R are each independently a substituent containing a partial structure containing an aromatic ring, and R 1is a hydrogen atom or a methyl group. In the present specification, in the constitutional units represented by Structures (1) to (6), the portion other than R is the main chain of a specific polymer. The formula weight of the substituent R is 80 or more, preferably 100 or more, more preferably 130 or more, and even more preferably 150 or more. The upper limit of the formula weight of the substituent R is practically 500 or less.
[0147] The polymer having a polymerizable functional group is usually a compound having a weight average molecular weight of 500 or more, preferably 1,000 or more, more preferably 2,000 or more. The upper limit of the weight average molecular weight is not particularly specified, but is preferably 50,000 or less. By making the weight average molecular weight equal to or greater than the above-mentioned lower limit, the boiling point can be made 250°C or more, and the mechanical properties after curing can be further improved. In addition, by making the weight average molecular weight equal to or less than the above-mentioned upper limit, the solubility in the solvent is high, the viscosity is not too high, and the fluidity of the droplets that are discretely arranged can be maintained, and the flatness of the liquid film plane can be further improved. In addition, the weight average molecular weight (Mw) in the present invention refers to that measured by gel permeation chromatography (GPC) unless otherwise specified.
[0148] Specific examples of the polymerizable functional group of the polymer include a (meth)acryloyl group, an epoxy group, an oxetane group, a methylol group, a methylol ether group, a vinyl ether group, etc. From the viewpoint of ease of polymerization, a (meth)acryloyl group is particularly preferred.
[0149] When a polymer having a polymerizable functional group is added as at least a part of component (a), the blending ratio can be freely set as long as it falls within the range of the viscosity regulation described later. For example, it is preferably 0.1% by weight or more and 60% by weight or less, more preferably 1% by weight or more and 50% by weight or less, and even more preferably 10% by weight or more and 40% by weight or less, based on the total mass of all components except for the solvent (d). By setting the blending ratio of the polymer having a polymerizable functional group to 0.1% by weight or more, it is possible to improve heat resistance, dry etching resistance, mechanical strength, and low volatility. In addition, by setting the blending ratio of the polymer having a polymerizable functional group to 60% by weight or less, it is possible to fall within the upper limit of the viscosity regulation described later.
[0150] <Component (b): Photopolymerization initiator> Component (b) is a photopolymerization initiator. In this specification, a photopolymerization initiator is a compound that senses light of a specific wavelength and generates the above-mentioned polymerization factor (radical). Specifically, a photopolymerization initiator is a polymerization initiator (radical generator) that generates radicals by light (infrared rays, visible light, ultraviolet rays, far ultraviolet rays, charged particle rays such as X-rays and electron beams, radiation). Component (b) may be composed of only one type of photopolymerization initiator, or may be composed of multiple types of photopolymerization initiators.
[0151] Examples of the radical generator include, but are not limited to, the following: 2,4,5-Triarylimidazole dimers which may have a substituent, such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, and 2-(o- or p-methoxyphenyl)-4,5-diphenylimidazole dimer; benzophenone, N,N'-tetramethyl-4,4'-diaminobenzophenone (Michler's ketone), N,N'-tetraethyl-4,4'-diaminobenzophenone, benzophenone derivatives such as 4-methoxy-4'-dimethylaminobenzophenone, 4-chlorobenzophenone, 4,4'-dimethoxybenzophenone, and 4,4'-diaminobenzophenone; α-amino aromatic ketone derivatives such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one; 2-ethylanthraquinone, phenanthrenequinone, 2-t-butylanthraquinone, octamethylanthraquinone, 1,2-benzo Quinones such as anthraquinone, 2,3-benzanthraquinone, 2-phenylanthraquinone, 2,3-diphenylanthraquinone, 1-chloroanthraquinone, 2-methylanthraquinone, 1,4-naphthoquinone, 9,10-phenanthraraquinone, 2-methyl-1,4-naphthoquinone, and 2,3-dimethylanthraquinone; benzoin ether derivatives such as benzoin methyl ether, benzoin ethyl ether, and benzoin phenyl ether; benzoin derivatives such as benzoin, methylbenzoin, ethylbenzoin, and propylbenzoin; benzyl benzyl derivatives such as dimethyl ketal; acridine derivatives such as 9-phenylacridine and 1,7-bis(9,9'-acridinyl)heptane; N-phenylglycine derivatives such as N-phenylglycine; acetophenone derivatives such as acetophenone, 3-methylacetophenone, acetophenone benzyl ketal, 1-hydroxycyclohexyl phenyl ketone, and 2,2-dimethoxy-2-phenylacetophenone; thioxanthone derivatives such as thioxanthone, diethylthioxanthone, 2-isopropylthioxanthone, and 2-chlorothioxanthone;Acylphosphine oxide derivatives such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; oxime ester derivatives such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime); xanthone, fluorenone, benzaldehyde, fluorene, anthraquinone, triphenylamine, carbazole, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; Examples of commercially available radical generators include, but are not limited to, the following: Irgacure 184, 369, 651, 500, 819, 907, 784, 2959, CGI-1700, -1750, -1850, CG24-61, Darocur 1116, 1173, Lucirin (registered trademark) TPO, LR8893, LR8970 (all manufactured by BASF), Ubecryl P36 (manufactured by UCB) Of the above-mentioned radical generators, the component (b) is preferably an acylphosphine oxide-based polymerization initiator. Among the above-mentioned radical generators, the acylphosphine oxide-based polymerization initiator is as follows. Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide The blending ratio of component (b) in the curable composition (A) is preferably 0.1% by weight or more and 50% by weight or less based on the total mass of components (a), (b), and (c) described later, i.e., the total mass of all components excluding the solvent (d). The blending ratio of component (b) in the curable composition (A) is more preferably 0.1% by weight or more and 20% by weight or less, and even more preferably 1% by weight or more and 20% by weight or less based on the total mass of all components excluding the solvent (d). By making the blending ratio of component (b) 0.1% by weight or more, the curing speed of the composition can be increased and the reaction efficiency can be improved. In addition, by making the blending ratio of component (b) 50% by weight or less, a cured film having a certain degree of mechanical strength can be obtained.
[0152] <Component (c): Non-polymerizable compound> In addition to the above-mentioned components (a) and (b), the curable composition (A) of the present invention may further contain a non-polymerizable compound as component (c) according to various purposes, within the scope of not impairing the effects of the present invention. Examples of such component (c) include compounds that do not have a polymerizable functional group such as a (meth)acryloyl group and do not have the ability to sense light of a certain wavelength and generate the above-mentioned polymerization factor (radical). Examples of the non-polymerizable compound include a sensitizer, a hydrogen donor, a surfactant (c1), an antioxidant, a polymer component, and other additives. Component (c) may contain multiple types of the above-mentioned compounds.
[0153] The sensitizer is a compound that is appropriately added for the purpose of promoting the polymerization reaction and improving the reaction conversion rate. The sensitizer may be used alone or in combination of two or more kinds.
[0154] Examples of the sensitizer include sensitizing dyes. The sensitizing dye is a compound that is excited by absorbing light of a specific wavelength and interacts with the photopolymerization initiator, which is component (b). Here, the interaction refers to energy transfer or electron transfer from the excited sensitizing dye to the photopolymerization initiator, which is component (b). Specific examples of the sensitizing dye include, but are not limited to, the following: Anthracene derivatives, anthraquinone derivatives, pyrene derivatives, perylene derivatives, carbazole derivatives, benzophenone derivatives, thioxanthone derivatives, xanthone derivatives, coumarin derivatives, phenothiazine derivatives, camphorquinone derivatives, acridine dyes, thiopyrylium salt dyes, merocyanine dyes, quinoline dyes, styrylquinoline dyes, ketocoumarin dyes, thioxanthene dyes, xanthene dyes, oxonol dyes, cyanine dyes, rhodamine dyes, pyrylium salt dyes The hydrogen donor is a compound that reacts with the initiation radicals generated from the photopolymerization initiator, component (b), or with radicals at the polymer growth terminal, to generate radicals with higher reactivity. When the photopolymerization initiator, component (b), is a photoradical generator, it is preferable to add a hydrogen donor.
[0155] Specific examples of such hydrogen donors include, but are not limited to, the following: Amine compounds such as n-butylamine, di-n-butylamine, tri-n-butylphosphine, allylthiourea, s-benzylisothiuronium-p-toluenesulfinate, triethylamine, diethylaminoethyl methacrylate, triethylenetetramine, 4,4'-bis(dialkylamino)benzophenone, N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid isoamyl ester, pentyl-4-dimethylaminobenzoate, triethanolamine, and N-phenylglycine; mercapto compounds such as 2-mercapto-N-phenylbenzimidazole and mercaptopropionic acid ester. The hydrogen donor may be used alone or in combination of two or more kinds. The hydrogen donor may also function as a sensitizer.
[0156] In the present invention, a surfactant (c1) is added to the curable composition (A) for the purpose of suppressing extrusion and seepage. The surfactant (c1) also functions as an internal mold release agent that reduces the interfacial bonding strength between the mold and the curable composition, that is, reduces the mold release force in the mold release step described below. In this specification, the internal mold means that it is added to the curable composition in advance before the placement step of the curable composition. As the surfactant (c1), a surfactant such as a silicon-based surfactant, a fluorine-based surfactant, and a hydrocarbon-based surfactant can be used. However, in the present invention, the surfactant (c1) has a limited amount to be added, as described below. The surfactant (c1) in the present invention is not polymerizable. The surfactant (c1) may be used alone or in a mixture of two or more types.
[0157] Fluorosurfactants include the following: Polyalkylene oxide (polyethylene oxide, polypropylene oxide, etc.) adducts of alcohols having perfluoroalkyl groups, polyalkylene oxide (polyethylene oxide, polypropylene oxide, etc.) adducts of perfluoropolyethers The fluorosurfactant may have a hydroxyl group, an alkoxy group, an alkyl group, an amino group, a thiol group, etc. in a part of the molecular structure (for example, a terminal group). For example, pentadecaethylene glycol mono 1H,1H,2H,2H-perfluorooctyl ether, etc. can be mentioned.
[0158] As the fluorosurfactant, commercially available products may be used. Examples of commercially available fluorosurfactants include the following: Megafac (registered trademark) F-444, TF-2066, TF-2067, TF-2068, abbreviated as DEO-15 (all manufactured by DIC), Fluorard FC-430, FC-431 (all manufactured by Sumitomo 3M), Surflon (registered trademark) S-382 (manufactured by AGC), EFTOP EF-122A, 122B, 122C, EF-121, EF-126, EF-127, MF-100 (all manufactured by Tochem Products), PF-636, PF-6320, PF-656, PF-6520 (all manufactured by OMNOVA Solutions), Unidyne (registered trademark) DS-401, DS-403, DS-451 (all manufactured by Daikin Industries), Futergent (registered trademark) 250, 251, 222F, 208G (all manufactured by Neos) The surfactant (c1) may be a hydrocarbon surfactant. Examples of the hydrocarbon surfactant include an alkyl alcohol polyalkylene oxide adduct in which an alkylene oxide having 2 to 4 carbon atoms is added to an alkyl alcohol having 1 to 50 carbon atoms, and a polyalkylene oxide.
[0159] Examples of the alkyl alcohol polyalkylene oxide adducts include the following. Methyl alcohol ethylene oxide adduct, decyl alcohol ethylene oxide adduct, lauryl alcohol ethylene oxide adduct, cetyl alcohol ethylene oxide adduct, stearyl alcohol ethylene oxide adduct, stearyl alcohol ethylene oxide / propylene oxide adduct The terminal group of the alkyl alcohol polyalkylene oxide adduct is not limited to a hydroxyl group that can be produced by simply adding a polyalkylene oxide to an alkyl alcohol. Such a hydroxyl group may be substituted with other substituents, for example, polar functional groups such as a carboxyl group, an amino group, a pyridyl group, a thiol group, or a silanol group, or hydrophobic functional groups such as an alkyl group or an alkoxy group.
[0160] Examples of the polyalkylene oxide include the following. Polyethylene glycol, polypropylene glycol, their mono- or dimethyl ethers, mono- or dioctyl ethers, mono- or dinonyl ethers, mono- or didecyl ethers, monoadipate esters, monooleate esters, monostearate esters, monosuccinate esters The alkyl alcohol polyalkylene oxide adduct may be a commercially available product. Examples of commercially available alkyl alcohol polyalkylene oxide adducts include the following: Polyoxyethylene methyl ether (methyl alcohol ethylene oxide adduct) (BLAUNON MP-400, MP-550, MP-1000) manufactured by Aoki Oil Industry Co., Ltd., polyoxyethylene decyl ether (decyl alcohol ethylene oxide adduct) (FINESURF D-1303, D-1305, D-1307, D-1310) manufactured by Aoki Oil Industry Co., Ltd., polyoxyethylene lauryl ether (lauryl alcohol ethylene oxide adduct) (BLAUNON EL-1505) manufactured by Aoki Oil Industry Co., Ltd., polyoxyethylene cetyl ether (cetyl alcohol ethylene oxide adduct) (BLAUNON CH-305, CH-310) manufactured by Aoki Oil Industry Co., Ltd., polyoxyethylene stearyl ether (stearyl alcohol ethylene oxide adduct) (BLAUNON SR-705, SR-707, SR-715, SR-720, SR-730, SR-750), random polymerization type polyoxyethylene polyoxypropylene stearyl ether (BLAUNON SA-50 / 50 1000R, SA-30 / 70 2000R) manufactured by Aoki Oil Industries, polyoxyethylene methyl ether (Pluriol(R) A760E) manufactured by BASF, polyoxyethylene alkyl ether (Emulgen series) manufactured by Kao Moreover, the polyalkylene oxide may be a commercially available product, for example, ethylene oxide-propylene oxide copolymer (Pluronic PE6400) manufactured by BASF.
[0161] The surfactant (c1) may be a silicone surfactant, such as SI-10 series (Takemoto Yushi Co., Ltd.), Megafac Paintad 31 (Dainippon Ink and Chemicals, Inc.), or KP-341 (Shin-Etsu Chemical Co., Ltd.).
[0162] The surfactant (c1) may be a surfactant containing at least both a fluorine atom and a silicon atom. Examples of surfactants containing both a fluorine atom and a silicon atom include the following. Product names: X-70-090, X-70-091, X-70-092, X-70-093 (all manufactured by Shin-Etsu Chemical Co., Ltd.), Product names: Megafaq R-08, XRB-4 (all manufactured by Dainippon Ink and Chemicals Co., Ltd.) The blending ratio of component (c) excluding surfactant in the curable composition (A) is preferably 0.01% by weight or more and 50% by weight or less based on the total mass of components (a), (b), and (c), i.e., the total mass of all components excluding solvent (d). The blending ratio of component (c) excluding surfactant in the curable composition (A) is more preferably 0.01% by weight or more and 50% by weight or less based on the total mass of all components excluding solvent (d), and more preferably 0.01% by weight or more and 20% by weight or less. By making the blending ratio of component (c) excluding surfactant 50% by weight or less, a cured film having a certain degree of mechanical strength can be obtained.
[0163] The upper limit of the blending ratio of the surfactant (c1) in the present invention is determined by the surface tension of the composition obtained by removing the solvent (d) from the curable composition (A) and the contact angle with the surface of the substrate and the surface of the mold, as described below. By making the blending ratio of the surfactant (c1) 0.01% by weight or more, the effects of the present invention can be obtained.
[0164] <Component (d): Solvent> The curable composition of the present invention contains, as component (d), a solvent having a boiling point of 100° C. or more and less than 250° C. under normal pressure. Examples of component (d) include solvents in which components (a), (b) and (c) dissolve, such as alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents and nitrogen-containing solvents. Component (d) can be used alone or in combination of two or more. The boiling point of component (d) under normal pressure is 100° C. or more, preferably 140° C. or more, and particularly preferably 150° C. or more. The boiling point of component (d) under normal pressure is less than 250° C., preferably less than 200° C. If the boiling point of component (d) under normal pressure is less than 100° C., the volatilization rate in the waiting step described below is too fast, so that component (d) volatilizes before droplets of the curable composition (A) bond together, and the droplets of the curable composition (A) may not bond together. Furthermore, if the boiling point of component (d) under normal pressure is 250° C. or higher, the solvent (d) may not volatilize sufficiently in the waiting step described below, and component (d) may remain in the cured product of the curable composition (A). Here, when component (d) contains one or more solvents, the boiling point of each of the one or more solvents under normal pressure is preferably 100° C. or higher and lower than 250° C. (e.g., 100° C. or higher and lower than 200° C.).
[0165] Examples of alcohol-based solvents include the following: Methanol, ethanol, n-propanol, iso-propanol, n-butanol, iso-butanol, sec-butanol, tert-butanol, n-pentanol, iso-pentanol, 2-methylbutanol, sec-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, 2-ethylbutanol, sec-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,6-dimethylheptanol-4, n-decanol, sec-undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl Monoalcohol solvents such as alcohol, sec-heptadecyl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, phenylmethylcarbinol, diacetone alcohol, and cresol; polyhydric alcohol solvents such as ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, and glycerin. Examples of ketone solvents include the following: Acetone, methyl ethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, diethyl ketone, methyl iso-butyl ketone, methyl n-pentyl ketone, ethyl n-butyl ketone, methyl n-hexyl ketone, di-iso-butyl ketone, trimethylnonanone, cyclohexanone, methylcyclohexanone, 2,4-pentanedione, acetonylacetone, diacetone alcohol, acetophenone, fenchone Examples of ether solvents include the following: Ethyl ether, isopropyl ether, n-butyl ether, n-hexyl ether, 2-ethylhexyl ether, ethylene oxide, 1,2-propylene oxide, dioxolane, 4-methyldioxolane, dioxane, dimethyldioxane, 2-methoxyethanol, 2-ethoxyethanol, ethylene glycol diethyl ether, 2-n-butoxyethanol, 2-n-hexoxyethanol, 2-phenoxyethanol, 2-(2-ethylbutoxy)ethanol, ethylene glycol dibutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol diethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol di-n-butyl ether, diethylene glycol mono-n-hexyl ether, ethoxytriglycol, tetraethylene glycol di-n-butyl ether, 1-n-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, tripropylene glycol monomethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran Examples of ester-based solvents include the following: Diethyl carbonate, methyl acetate, ethyl acetate, amyl acetate, gamma-butyrolactone, gamma-valerolactone, n-propyl acetate, iso-propyl acetate, n-butyl acetate, iso-butyl acetate, sec-butyl acetate, n-pentyl acetate, sec-pentyl acetate, 3-methoxybutyl acetate, methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, benzyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, n-nonyl acetate, methyl acetoacetate, ethyl acetoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl acetate Ether, Diethylene glycol mono-n-butyl ether acetate, Propylene glycol monomethyl ether acetate, Propylene glycol monoethyl ether acetate, Propylene glycol monopropyl ether acetate, Propylene glycol monobutyl ether acetate, Dipropylene glycol monomethyl ether acetate, Dipropylene glycol monoethyl ether acetate, Glycol diacetate, Methoxytriglycol acetate, Ethyl propionate, N-butyl propionate, Iso-amyl propionate, Diethyl oxalate, Di-n-butyl oxalate, Methyl lactate, Ethyl lactate, N-butyl lactate, N-amyl lactate, Diethyl malonate, Dimethyl phthalate, Diethyl phthalate Examples of the nitrogen-containing solvent include the following: N-Methylformamide, N,N-Dimethylformamide, N,N-Diethylformamide, Acetamide, N-Methylacetamide, N,N-Dimethylacetamide, N-Methylpropionamide, N-Methylpyrrolidone Among the above-mentioned solvents, ether-based solvents and ester-based solvents are preferred. From the viewpoint of excellent film-forming properties, more preferred solvents include ether-based solvents and ester-based solvents having a glycol structure.
[0166] More preferred examples include the following: Propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate Furthermore, particularly preferred is propylene glycol monomethyl ether acetate. Other examples include ethyl isocyanurate di(meth)acrylate.
[0167] In the present invention, a preferred solvent is a solvent having at least one of an ester structure, a ketone structure, a hydroxyl group, and an ether structure, specifically, a single solvent selected from propylene glycol monomethyl ether acetate (boiling point 146° C.), propylene glycol monomethyl ether, cyclohexanone, 2-heptanone, γ-butyrolactone, and ethyl lactate, or a mixture thereof.
[0168] In the present invention, a polymerizable compound having a boiling point of 80° C. or more and less than 250° C. under normal pressure can also be used as component (d). Examples of the polymerizable compound having a boiling point of 80° C. or more and less than 250° C. under normal pressure include the following. Cyclohexyl acrylate (198°C), benzyl acrylate (229°C), isobornyl acrylate (245°C), tetrahydrofurfuryl acrylate (202°C), trimethylcyclohexyl acrylate (232°C), isooctyl acrylate (217°C), n-octyl acrylate (228°C), ethoxyethoxyethyl acrylate (boiling point 230°C), divinylbenzene (193°C), 1,3-diisopropenylbenzene (218°C), styrene (145°C), α-methylstyrene (165°C) In the present invention, when the entire curable composition (A) is taken as 100 volume %, the content of the solvent (d) is more than 5 volume % and not more than 95 volume %, preferably 15 volume % or more and not more than 85 volume %, more preferably 40 volume % or more and not more than 80 volume %. For example, the content of the solvent (d) is 40 volume % or more and not more than 85 volume %. If the content of the solvent (d) is less than 5 volume %, a thin film cannot be obtained after the solvent (d) evaporates under conditions in which a substantially continuous liquid film is obtained. Also, if the content of the solvent (d) is more than 95 volume %, a thick film cannot be obtained after the solvent (d) evaporates even if droplets are dropped in close contact by the inkjet method.
[0169] <Temperature when compounding the curable composition> In preparing the curable composition (A) of the present invention, at least the components (a), (b) and (d) are mixed and dissolved under a predetermined temperature condition. Specifically, the predetermined temperature condition is in the range of 0° C. or higher and 100° C. or lower. The same applies when the curable composition (A) contains the component (c).
[0170] <Viscosity of Curable Composition> The curable composition (A) in the present invention is liquid. This is because droplets of the curable composition (A) are dropped discretely onto a substrate by an inkjet method in the disposing step described below. The viscosity of the curable composition (A) in the present invention is 1.3 mPa·s to 60 mPa·s at 23°C and 1 atm, preferably 2 mPa·s to 30 mPa·s, and more preferably 5 mPa·s to 15 mPa·s. If the viscosity of the curable composition (A) is less than 2 mPa·s, the ejection of droplets by the inkjet method becomes unstable. If the viscosity of the curable composition (A) is more than 60 mPa·s, droplets having a volume of about 1.0 to 3.0 pL, which is preferred in the present invention, cannot be formed.
[0171] The state after the solvent (d) has evaporated from the curable composition (A), that is, the viscosity of the mixture of the components of the curable composition (A) excluding the solvent (d) at 23°C and 1 atm is 30 mPa·s or more and 10,000 mPa·s or less. The viscosity of the mixture of the components of the curable composition (A) excluding the solvent (d) at 23°C and 1 atm is preferably 90 mPa·s or more and 2,000 mPa·s or less, for example, 120 mPa·s or more and 1000 mPa·s or less. Furthermore, the viscosity of the mixture of the components of the curable composition (A) excluding the solvent (d) at 23°C and 1 atm is more preferably 150 mPa·s or more and 500 mPa·s or less. By making the viscosity of the components of the curable composition (A) excluding the solvent (d) 1000 mPa·s or less, the spreading and filling are quickly completed when the curable composition (A) is brought into contact with the mold. Therefore, by using the curable composition (A) of the present invention, the imprint process can be performed with high throughput, and pattern defects due to insufficient filling can be suppressed. In addition, by making the viscosity of the components of the curable composition (A) other than the solvent (d) 1 mPa·s or more, it is possible to prevent unwanted flow of droplets of the curable composition (A) after the solvent (d) has evaporated. Furthermore, when the curable composition (A) is brought into contact with a mold, the curable composition (A) is less likely to flow out from the edge of the mold.
[0172] <Surface tension of curable composition> The surface tension γ1 in the state after the solvent (d) has evaporated from the curable composition (A) in the present invention is preferably 5 mN / m or more and 70 mN / m or less at 23°C and 1 atm. In addition, for the composition of components other than the solvent (component (d)), the surface tension at 23°C and 1 atm is more preferably 7 mN / m or more and 50 mN / m or less, and even more preferably 10 mN / m or more and 40 mN / m or less. In addition, the higher the surface tension, for example, 5 mN / m or more, the stronger the capillary force works, so that when the curable composition (A) is brought into contact with the mold, filling (spreading and filling) is completed in a short time. In addition, by setting the surface tension to 70 mN / m or less, the cured film obtained by curing the curable composition becomes a cured film having surface smoothness.
[0173] In the present invention, when the surface tension of the curable composition at 23°C in a state where the solvent (d) is removed is γ1 [mN / m], and the surface tension of the solvent (d) at 23°C is γ2 [mN / m], the curable composition is configured so that γ1 is greater than γ2. In other words, when Δγ=γ1-γ2, the curable composition is configured so that Δγ is greater than zero. Specifically, the solvent (d) is selected so that Δγ is greater than zero. When Δγ is greater than zero, the spreading of the droplets of the curable composition is accelerated by the Marangoni effect in the waiting step described below, and the droplets are quickly bonded to each other to form a continuous liquid film. In addition, the rapid spreading of the droplets accelerates the evaporation of the solvent, so that the waiting step described below can be completed in a short time, and the conditions of the baking step can be relaxed or omitted. Δγ is preferably 0.1 or more, particularly preferably 1.0 or more, and even more preferably 2.0 or more. Note that γ1 and γ2 are the surface tensions under normal pressure (1 atm).
[0174] <Contact angle of curable composition> The contact angle of the curable composition (A) in the present invention is preferably 0° or more and 90° or less with respect to both the surface of the substrate and the surface of the mold for the composition of components other than the solvent (component (d)). If the contact angle is greater than 90°, the capillary force acts in the negative direction (the direction that shrinks the contact interface between the mold and the curable composition) inside the pattern of the mold or in the gap between the substrate and the mold, and the curable composition (A) may not fill the mold. The smaller the contact angle, the stronger the capillary force acts, and the faster the filling speed becomes.
[0175] Regarding the contact angle of the curable composition (A) in the present invention, the contact angle of the composition of the components excluding the solvent (component (d)) and the surfactant (c1) with respect to the surface of the substrate is α1 [°], and the contact angle of the composition of the components excluding the solvent (component (d)) with respect to the surface of the substrate is α2 [°]. In this case, the type and amount of the surfactant (c1) are selected so that α2 is larger than α1. Specifically, by selecting the surfactant (c1) so that α2 is larger than α1, a pinning effect is exerted on the spreading of the droplets, and the spreading of the droplets on the substrate can be stopped at a desired size, and the amount of overflow of the curable composition can be suppressed.
[0176] In addition, with regard to the contact angle of the curable composition (A) in the present invention, when the composition of the components excluding the solvent (component (d)) is expressed as β [°] with respect to the surface of the mold, the type and amount of the surfactant (c1) are selected so that β is 25° or more. Specifically, by selecting the surfactant (c1) so that β is 25° or more, a pinning effect is exerted on the spreading of the droplets, and seepage can be suppressed. β is preferably 30° or more, and more preferably 40° or more.
[0177] <Impurities contained in the curable composition> It is preferable that the curable composition (A) in the present invention does not contain impurities as much as possible. Here, the impurities mean those other than the above-mentioned components (a), (b), (c) and (d). Therefore, it is preferable that the curable composition (A) in the present invention is obtained through a purification process. As such a purification process, filtration using a filter or the like is preferable.
[0178] As for the filtration using a filter, it is preferable to mix the above-mentioned components (a), (b) and (c) and then filter them with a filter having a pore size of 0.001 μm or more and 5.0 μm or less. When performing filtration using a filter, it is more preferable to perform the filtration in multiple stages or to repeat the filtration many times (circulation filtration). In addition, the liquid filtered through the filter may be filtered again, or may be filtered using multiple filters having different pore sizes. Examples of filters used for filtration include filters made of polyethylene resin, polypropylene resin, fluororesin, nylon resin, etc., but are not particularly limited. By going through such a purification process, impurities such as particles mixed in the curable composition can be removed. This can prevent impurities mixed in the curable composition from accidentally causing unevenness in the cured film obtained after curing the curable composition, which can cause defects in the pattern.
[0179] When the curable composition of the present invention is used to manufacture a semiconductor integrated circuit, it is preferable to avoid impurities containing metal atoms (metal impurities) from being mixed into the curable composition as much as possible so as not to hinder the operation of the product. The concentration of metal impurities contained in the curable composition is preferably 10 ppm or less, more preferably 100 ppb or less.
[0180] <Glass Transition Temperature of Curable Composition> If the glass transition temperature is sufficiently higher than the temperature at the time of demolding, the cured product at the time of demolding is in a strong glass state, i.e., exhibits high mechanical strength, so that the pattern is less likely to collapse or break due to the impact of demolding. Therefore, when the demolding step is carried out at room temperature, the glass transition temperature of the cured product (after curing of the polymerizable compound (a)) is preferably 70°C or higher, more preferably 100°C or higher, and particularly preferably 150°C or higher.
[0181] As a method for measuring the glass transition temperature of a cured product (photocured product), a method using a differential scanning calorimetry (DSC) or a dynamic viscoelasticity device can be applied. For example, consider the case where the glass transition temperature is measured using DSC. In this case, a straight line is obtained by extending the low-temperature side baseline (the DSC curve part in the temperature range where the transition and reaction do not occur in the test piece) of the DSC curve of the cured product to the high-temperature side, and a tangent line is drawn at the point where the gradient of the curve of the stepwise change part of the glass transition is maximum. Then, the extrapolated glass transition onset temperature (Tig) is obtained from the intersection point of the straight line and the tangent line, and this can be determined as the glass transition temperature. The main device is STA-6000 (manufactured by Perkin Eimer), etc. On the other hand, when the glass transition temperature is measured using a dynamic viscoelasticity device, the temperature at which the loss sine (tan δ) of the cured product is maximum is defined as the glass transition temperature. The main device for measuring dynamic viscoelasticity is MCR301 (manufactured by Anton Paar), etc.
[0182] [substrate] In this specification, the member onto which the droplets of the curable composition (A) are discretely dispensed is described as a substrate.
[0183] The substrate is a substrate to be processed, and is usually a silicon wafer. The substrate may have a layer to be processed on the surface. The substrate may have another layer formed below the layer to be processed. In addition, if a quartz substrate is used as the substrate, a replica (replica mold) of a mold for imprinting can be produced. However, the substrate is not limited to a silicon wafer or a quartz substrate. The substrate can be arbitrarily selected from those known as substrates for semiconductor devices, such as aluminum, titanium-tungsten alloy, aluminum-silicon alloy, aluminum-copper-silicon alloy, silicon oxide, and silicon nitride. The surface of the substrate or the layer to be processed may be improved in adhesion to the curable composition (A) by surface treatment such as silane coupling treatment, silazane treatment, and formation of an organic thin film. As a specific example of an organic thin film to be formed as a surface treatment, for example, an adhesion layer described in JP-T-2009-503139 can be used.
[0184] [Pattern formation method] The pattern forming method of the present invention will be described with reference to FIG. 1(a) to FIG. 1(g). The cured film formed by the present invention is preferably a film having a pattern of 1 nm to 10 mm, more preferably a film having a pattern of 10 nm to 100 μm. In general, a film forming method for forming a film having a nano-sized pattern (uneven structure) (1 nm to 100 nm) using light is called a photoimprint method. The film forming method of the present invention uses the photoimprint method to form a film of a curable composition in the space between a mold and a substrate. However, the curable composition may be cured by other energy (e.g., heat, electromagnetic waves). In addition, the film forming method of the present invention may be implemented as a method for forming a film having a pattern, i.e., a pattern forming method, or a method for forming a film without a pattern (e.g., a planarized film), i.e., a planarized film forming method.
[0185] Hereinafter, an example in which the film formation method of the present invention is applied to a pattern formation method will be described. The pattern formation method includes, for example, a formation step, a disposition step, a waiting step, a contact step, a curing step, and a demolding step. The formation step is a step of forming an underlayer. The disposition step is a step of disposing droplets of the curable composition (A) discretely on the underlayer. The waiting step is a step of waiting until the droplets of the curable composition (A) are bonded to each other and the solvent (d) is evaporated. The contact step is a step of contacting the curable composition (A) with a mold. The curing step is a step of curing the curable composition (A). The demolding step is a step of separating the mold from the cured film of the curable composition (A). The disposition step is performed after the formation step, the waiting step is performed after the disposition step, the contact step is performed after the waiting step, the curing step is performed after the contact step, and the demolding step is performed after the curing step.
[0186] <Placement process> In the disposing step, as shown in FIG. 1(a), droplets 102 of the curable composition (A) are discretely disposed on a substrate 101. In the disposing step, droplets 102 of the curable composition (A) having a volume of 1.0 pL or more are disposed at a density of 80 droplets / mm 2 The substrate 101 is arranged at a density of at least 100 nm. A substrate having a base layer laminated thereon may be used as the substrate 101. The surface of the substrate 101 may be subjected to a surface treatment such as a silane coupling treatment, a silazane treatment, or the formation of an organic thin film to improve adhesion to the curable composition (A).
[0187] The inkjet method is particularly preferred as a method for disposing the droplets 102 of the curable composition (A) on the substrate. The droplets 102 of the curable composition (A) are preferably densely disposed on the region of the substrate 101 facing the region where the recesses constituting the pattern of the mold 106 are densely present, and sparsely disposed on the region of the substrate 101 facing the region where the recesses constituting the pattern of the mold 106 are sparsely present. This allows the film (residual film) 109 of the curable composition (A) described later formed on the substrate 101 to be controlled to a uniform thickness regardless of the density of the pattern of the mold 106.
[0188] In order to define the volume of the curable composition (A) to be placed, an index called the average remaining liquid film thickness is defined. The average remaining liquid film thickness is the value obtained by dividing the volume of the curable composition (A) (excluding the solvent (d)) placed in the placing step by the area of the film-forming region of the mold. The volume of the curable composition (A) (excluding the solvent (d)) is the sum of the volumes of the individual droplets of the curable composition (A) after the solvent (d) has evaporated. According to this definition, even if the substrate surface has unevenness, the average remaining liquid film thickness can be defined regardless of the unevenness. Here, the average remaining liquid film thickness may be understood as the value obtained by dividing the volume of the curable composition (A) remaining after the waiting step described below by the area of the film-forming region of the mold, and is preferably 20 nm or less.
[0189] <Standby process> In the present invention, a waiting step is provided after the placing step and before the contacting step. Here, the average initial liquid film thickness is defined as the total volume of the droplets of the curable composition (A) dispensed in one pattern formation divided by the total area of the region where a pattern is formed in one pattern formation (pattern formation region). In the waiting step, the droplets 102 of the curable composition (A) spread on the substrate 101 as shown diagrammatically in FIG. 1(b). As a result, the entire pattern formation region of the substrate 101 is covered with the curable composition (A).
[0190] As described above, in the present invention, when the surface tension of the curable composition from which the solvent (d) has been removed is γ1 [mN / m] and the surface tension of the solvent (d) is γ2 [mN / m], the curable composition (A) is configured so that γ1 is greater than γ2. Specifically, the solvent (d) is selected so that γ1 is greater than γ2, so that the droplets 102 of the curable composition (A) dropped onto the substrate 101 spread widely (i.e., the spreading speed of the droplets 102 increases). The reason for this will be described below.
[0191] Since the droplets of the curable composition (A) dropped on the substrate contain volatile components, the concentration of the volatile components changes due to the evaporation after dropping. Since the surface tension γ1 of the non-volatile components is greater than the surface tension γ2 of the volatile components, when the concentration of the volatile components decreases with evaporation, the surface tension increases. In general, the droplets gradually spread out and stop spreading at the static contact angle, but the greater the difference between the contact angle with the substrate at the end of the droplet and the static contact angle, the greater the spreading speed. In addition, since the thickness of the cured film is very thin compared to the radius of the droplet, the concentration diffusion in the radial direction is much slower than the concentration diffusion in the thickness direction.
[0192] The behavior (behavior after dropping) of the droplet 102 of the curable composition (A) dropped on the substrate 101 will be described with reference to FIG. 2. FIG. 2 shows the state in which the droplet 102 dropped on the substrate spreads. As described above, the evaporation of the solvent component proceeds even while the droplet 102 spreads. The evaporation rate is largely dependent on the surface area of the droplet 102. Comparing the central portion 303 of the droplet 102 with the end portion 304 of the droplet 102, the surface area of the end portion 304 of the droplet 102 is slightly larger than the surface area of the central portion 303 of the droplet 102, so that the evaporation is faster. On the other hand, the volume of the droplet 102 is smaller at the end portion 304 of the droplet 102 than at the central portion 303 of the droplet 102. Therefore, the edge 304 of the droplet 102 volatilizes faster and has a smaller volume than the central portion 303 of the droplet 102, resulting in a lower concentration of volatile components and a higher surface tension. In this way, the edge 304 of the droplet 102 has a higher surface tension than the central portion 303 of the droplet 102, so a force is generated from the central portion 303 of the droplet 102 toward the edge 304 due to the Marangoni effect, inducing a flow (spreading) of the droplet 102.
[0193] Fig. 3 is a diagram showing the shape of the droplet 102 when a flow of the droplet 102 is induced by the Marangoni effect. When a flow of the droplet 102 is induced toward the end of the droplet 102, the end of the droplet 102 becomes swollen, as shown in Fig. 4. As a result, the contact angle between the end of the droplet 102 and the substrate 101 becomes larger than when the flow of the droplet 102 is not induced, and the spreading speed of the droplet 102 also increases.
[0194] As described above, the type and amount of the surfactant (c1) are selected so that the contact angle of the curable composition (A) is such that α2 [°] is larger than α1 [°]. Here, α1 is the contact angle of the composition of the components other than the solvent (component (d)) and the surfactant (c1) to the surface of the substrate 101, and α2 is the contact angle of the composition of the components other than the solvent (component (d)) to the surface of the substrate 101. Specifically, since the surfactant (c1) is selected so that α2 is larger than α1, a pinning effect is exerted on the spread of the droplet 102, and the spread of the droplet 102 on the substrate can be stopped at a desired size, and the amount of overflow can be suppressed. The cause of this will be described below.
[0195] FIG. 4 is a diagram showing a state where a droplet 102 of a curable composition (A) is dropped onto a substrate 101. The droplet 102 dropped onto the substrate 101 spreads while volatilizing, and when the curable composition (A) does not contain a surfactant (c1), the droplet 102 spreads to a contact angle α1 as shown in FIG. 5. In particular, when the contact angle α1 is close to zero, the droplet 102 continues to spread over a large area. On the other hand, when the curable composition (A) contains a surfactant (c1), the droplet 102 dropped onto the substrate 101 spreads to a contact angle α2 (α2>α1) as shown in FIG. 6. Comparing FIG. 5 and FIG. 6, the surfactant (c1) increases the contact angle from α1 to α2, and the droplet 102 is pinned in a region determined by the contact angle α2, stopping the spreading, so that the amount of overflow can be suppressed.
[0196] According to the examples described later, for example, a case is selected in which the solvent (d) is a highly volatile solvent with a volume ratio of non-volatile components of 20%, and the droplet pitch is 88 μm, i.e., the average initial liquid film thickness is 13 nm or more. In this case, as shown in FIG. 1(c), a numerical calculation has shown that the droplets of the curable composition (A) bond together on the substrate to form a substantially continuous liquid film 103. This is also achieved by forming droplets of the curable composition (A) with a volume of 1.0 pL or more at a density of 130 droplets / m 2 This means that the electrodes are arranged at a density of at least 100 nm.
[0197] With reference to Fig. 7(a) to Fig. 7(d), the flow behavior of the droplets of the curable composition (A) placed on the substrate during the waiting process will be described. As shown in Fig. 7(a), the droplets 102 of the curable composition (A) are discretely placed on the substrate 101, and as shown in Fig. 7(b), each droplet 102 gradually spreads on the substrate. Then, as shown in Fig. 7(c), the droplets of the curable composition (A) on the substrate start to combine with each other to form a liquid film, and as shown in Fig. 7(d), the liquid film becomes continuous (the surface of the substrate 101 is covered with the curable composition (A) and there is no exposed surface). The state of the curable composition (A) as shown in Fig. 7(d) is referred to as a "substantially continuous liquid film".
[0198] Furthermore, in the waiting step, as shown in Fig. 1(d), the solvent 105 (solvent (d)) contained in the liquid film 104 is volatilized. The amount of solvent (d) remaining in the liquid film 103 after the waiting step (e.g., at the start of the contacting step) is preferably 10% by volume or less, assuming that the total weight of the components other than the solvent (d) is 100% by volume. If the amount of solvent (d) remaining is more than 10% by volume, the mechanical properties of the cured film may be reduced.
[0199] In the waiting step, in order to accelerate the evaporation of the solvent (d), a baking step may be performed in which the substrate 101 and the curable composition (A) are heated, or the atmospheric gas around the substrate 101 may be ventilated. The heating is performed, for example, at 30°C or higher and 200°C or lower, preferably 80°C or higher and 150°C or lower, and particularly preferably 90°C or higher and 110°C. The heating time may be 10 seconds or higher and 600 seconds or lower. The baking step may be performed using a known heater such as a hot plate or an oven.
[0200] The waiting step is, for example, 0.1 to 600 seconds, preferably 10 to 300 seconds. If the waiting step is shorter than 0.1 seconds, the droplets of the curable composition (A) are not sufficiently bonded to each other, and a substantially continuous liquid film is not formed. If the waiting step exceeds 600 seconds, the productivity decreases. Therefore, in order to suppress the decrease in productivity, the substrates on which the arrangement step has been completed may be sequentially transferred to the waiting step, and the waiting step may be performed in parallel on a plurality of substrates, and the substrates on which the waiting step has been completed may be sequentially transferred to the contact step. In the prior art, it theoretically takes several thousand to several tens of thousands of seconds until a substantially continuous liquid film is formed, but in reality, the spread of the droplets of the curable composition stagnates due to the effect of volatilization, so that a continuous liquid film cannot be formed.
[0201] In the waiting step, when the solvent (d) volatilizes, a substantially continuous liquid film 104 consisting of the components (a), (b) and (c) remains. The average remaining liquid film thickness of the substantially continuous liquid film 104 from which the solvent (d) has been volatilized (removed) becomes thinner than the liquid film 103 by the amount of the solvent (d) that has been volatilized. The pattern formation region of the substrate 101 remains in a state of being covered over the entire region with the substantially continuous liquid film 104 of the curable composition (A) from which the solvent (d) has been removed.
[0202] <Contact process> In the contacting step, as shown in Fig. 1(e) as a schematic diagram, a substantially continuous liquid film 104 of the curable composition (A) from which the solvent (d) has been removed is brought into contact with the mold 106. The contacting step includes a step of changing a state in which the curable composition (A) and the mold 106 are not in contact with each other to a state in which they are in contact with each other, and a step of maintaining the state in which they are in contact with each other. As a result, the liquid of the curable composition (A) fills the recesses of the fine pattern on the surface of the mold 106, and the liquid becomes a liquid film that fills the fine pattern of the mold 106.
[0203] In the present invention, in the waiting step, the curable composition (A) becomes a substantially continuous liquid film 104 from which the solvent (d) has been removed, so that the volume of gas entrapped between the mold 106 and the substrate 101 is reduced. Therefore, the spreading of the curable composition (A) in the contact step is completed quickly. A comparison (difference) between the contact step in the prior art disclosed in Japanese Patent No. 6584578 and the contact step in the present invention is shown in FIG. 8.
[0204] If the spreading and filling of the curable composition (A) is completed quickly in the contacting step, the time required for maintaining the state in which the mold 106 is in contact with the curable composition (A) (the time required for the contacting step) can be shortened. Furthermore, shortening the time required for the contacting step leads to shortening the time required for pattern formation (film formation), thereby improving productivity. The contacting step is preferably from 0.1 to 3 seconds, and particularly preferably from 0.1 to 1 second. If the contacting step is shorter than 0.1 seconds, spreading and filling are insufficient, and defects called unfilled defects tend to occur frequently.
[0205] As described above, in the contact step, a phenomenon called seepage may occur. This is a phenomenon in which the curable composition protrudes from the contact surface of the mold and adheres (creeps up) to the side wall (side surface) of the mold in the contact step. The concept of seepage will be described with reference to FIG. 9. As shown in FIG. 16, the curable composition 1602 protruding from the mold 106 creeps up the side wall of the mold 106, and an unnecessary cured product of the curable composition 1602 is formed outside the contact surface of the mold 106, which causes a defect, that is, a so-called seepage (defect). Here, the height to which the curable composition 1602 creeps up the side wall of the mold 106 is defined as the seepage height 1604.
[0206] In the present invention, as described above, with respect to the contact angle of the curable composition (A), when the composition of the components excluding the solvent (component (d)) is β [°] with respect to the surface of the mold, the type and amount of the surfactant (c1) are selected so that β is 25° or more. The reason for this will be described with reference to FIG. 10. As described above, the curable composition 1602 that protrudes from the mold 106 creeps up the side wall of the mold 106, and when the contact angle β is smaller than 25°, for example, an interface 1705 as shown by a solid line in FIG. 10 is formed. The contact angle β between the mold 106 and the interface 1705 is β<25°. On the other hand, when the curable composition 1602 contains a surfactant and the contact angle β is 25° or more, for example, an interface 1706 as shown by a broken line in FIG. 10 is formed. The contact angle β between the mold 106 and the interface 1705 is β≧25°. Comparing interface 1705 and interface 1706, it can be seen that although the volume of curable composition 1602 protruding from mold 106 is greater at interface 1706, the seepage height is lower at interface 1706. In this way, by increasing the contact angle β, the dependency of the seepage height on the volume of curable composition 1602 protruding from mold 106 becomes weaker, and the seepage height can be suppressed. β is preferably 30° or more, and more preferably 40° or more.
[0207] When the curing step includes a light irradiation step, a mold made of a light-transmitting material is used as the mold 106 in consideration of this. Specific examples of the material constituting the mold 106 include glass, quartz, light-transmitting resins such as PMMA and polycarbonate resins, transparent metal deposition films, flexible films such as polydimethylsiloxane, light-curing films, and metal films. However, when a light-transmitting resin is used as the material constituting the mold 106, a resin that is not dissolved in the components contained in the curable composition is selected. Quartz is suitable as a material constituting the mold 106 because it has a small thermal expansion coefficient and small pattern distortion.
[0208] The pattern formed on the surface of the mold 106 has a height of, for example, 4 nm or more and 200 nm or less. The lower the height of the pattern of the mold 106, the smaller the force for separating the mold 106 from the cured film of the curable composition in the demolding step, i.e., the demolding force, and the number of demolding defects remaining on the mold 106 due to the pattern of the curable composition being torn off can be reduced. In addition, the impact when the mold is separated may cause the pattern of the curable composition to elastically deform, causing adjacent pattern elements to come into contact with each other, resulting in adhesion or damage. However, it is advantageous to have the height of the pattern element be about twice or less the width of the pattern element (aspect ratio 2 or less) in order to avoid such defects. On the other hand, if the height of the pattern element is too low, the processing accuracy of the substrate 101 will be reduced.
[0209] The mold 106 may be subjected to a surface treatment before the contact step is performed in order to improve the releasability of the mold 106 with respect to the curable composition (A). For example, the surface treatment may involve applying a release agent to the surface of the mold 106 to form a release agent layer. Examples of the release agent applied to the surface of the mold 106 include silicon-based release agents, fluorine-based release agents, hydrocarbon-based release agents, polyethylene-based release agents, polypropylene-based release agents, paraffin-based release agents, montan-based release agents, and carnauba-based release agents. For example, commercially available coating-type release agents such as Optool (registered trademark) DSX manufactured by Daikin Industries, Ltd. can also be suitably used. The release agents may be used alone or in combination of two or more types. Of the above-mentioned release agents, fluorine-based and hydrocarbon-based release agents are particularly preferred.
[0210] In the contact step, the pressure applied to the curable composition (A) when the mold 106 is brought into contact with the curable composition (A) is not particularly limited, and is, for example, 0 MPa or more and 100 MPa or less. Note that the pressure applied to the curable composition (A) when the mold 106 is brought into contact with the curable composition (A) is preferably 0 MPa or more and 50 MPa or less, more preferably 0 MPa or more and 30 MPa or less, and even more preferably 0 MPa or more and 20 MPa or less.
[0211] The contact step can be carried out under any of the conditions of air, reduced pressure, and inert gas atmosphere, but reduced pressure and inert gas atmospheres are preferred because they can prevent the influence of oxygen and moisture on the curing reaction. Specific examples of inert gases used when carrying out the contact step under an inert gas atmosphere include nitrogen, carbon dioxide, helium, argon, various fluorocarbon gases, and the like, or mixed gases thereof. Gases containing 10% or more of carbon dioxide or helium in molar ratio are preferred, and gases containing 10% or more of carbon dioxide in molar ratio are particularly preferred. Helium gas is easily diffused into the mold, substrate, curable composition, etc., so that atmospheric gas trapped in the mold pattern, etc., disappears quickly. Carbon dioxide is easily dissolved in the curable composition and the underlayer on the substrate, so that atmospheric gas trapped in the mold pattern, etc., disappears quickly. The solubility coefficient of carbon dioxide in the curable composition is 0.5 kg / m 3 ·ATM or more 10kg / m 3 The pressure is preferably 0.0001 atm or less. Details of these are disclosed in JP 2022-99271 A. When the contact step is performed under a specific gas atmosphere, including the air atmosphere, the preferred pressure is 0.0001 atm or more and 10 atm or less.
[0212] <Curing process> In the curing step, as shown in FIG. 1(f), the curable composition (A) is irradiated with irradiation light 107 as curing energy to cure the curable composition (A) and form a cured film. In the curing step, for example, the curable composition (A) is irradiated with irradiation light 107 through a mold 106. More specifically, the curable composition (A) filled in the fine pattern of the mold 106 is irradiated with irradiation light 107 through the mold 106. As a result, the curable composition (A) filled in the fine pattern of the mold 106 is cured to form a cured film 108 having a pattern.
[0213] The irradiation light 107 is selected according to the sensitivity wavelength of the curable composition (A). Specifically, the irradiation light 107 is appropriately selected from ultraviolet light, X-rays, or electron beams having a wavelength of 150 nm or more and 400 nm or less. It is particularly preferable that the irradiation light 107 is ultraviolet light. This is because many of the compounds commercially available as curing assistants (photopolymerization initiators) are sensitive to ultraviolet light. Examples of light sources that emit ultraviolet light include high-pressure mercury lamps, ultra-high-pressure mercury lamps, low-pressure mercury lamps, Deep-UV lamps, carbon arc lamps, chemical lamps, metal halide lamps, xenon lamps, KrF excimer lasers, ArF excimer lasers, and F2 lasers. However, the ultra-high-pressure mercury lamp is particularly preferable as the light source that emits ultraviolet light. The number of light sources may be one or more. The entire area of the curable composition (A) filled in the fine pattern of the mold may be irradiated with light, or only a part of the area (a limited area) may be irradiated with light. The light irradiation may be performed intermittently multiple times over the entire area of the substrate, or may be performed continuously over the entire area of the substrate. Furthermore, the first area of the substrate may be irradiated with light in the first irradiation process, and the second area of the substrate different from the first area may be irradiated with light in the second irradiation process.
[0214] <Mold release process> In the demolding step, as shown in FIG. 1(g), the mold 106 is separated from the cured film 108. By separating the patterned cured film 108 from the mold 106, the cured film 108 having a pattern that is an inversion of the fine pattern of the mold 106 is obtained in a free-standing state. Here, the cured film remains in the recesses of the patterned cured film 108. Such a film is called a residual film.
[0215] The method of separating the mold 106 from the cured film 108 having the pattern is not particularly limited as long as a part of the cured film 108 having the pattern is not physically damaged during the separation. For example, the substrate 101 may be fixed and the mold 106 may be moved away from the substrate 101. The mold 106 may be fixed and the substrate 101 may be moved away from the mold 106. The mold 106 may be separated from the cured film 108 having the pattern by moving both the mold 106 and the substrate 101 in opposite directions.
[0216] <Repeat> By a series of steps (manufacturing process) including the above-mentioned placement step through demolding step in this order, a cured film having a desired concave-convex pattern shape (a pattern shape that follows the concave-convex shape of the mold 106) in a desired position can be obtained.
[0217] In the pattern formation method of the present invention, the repeating unit (shot) from the placement step to the demolding step can be repeated multiple times on the same substrate, thereby obtaining a cured film 108 having multiple desired patterns at desired positions on the substrate.
[0218] [Planarization film formation method] Hereinafter, an example in which the film forming method of the present invention is applied to a planarizing film forming method will be described. The planarizing film forming method includes, for example, a disposing step, a waiting step, a contact step, a curing step, and a demolding step. The disposing step is a step of disposing droplets of the curable composition (A) on a substrate. The waiting step is a step of waiting until the droplets of the curable composition (A) are bonded to each other and the solvent (d) is evaporated. The contacting step is a step of contacting the curable composition (A) with a mold. The curing step is a step of curing the curable composition (A). The demolding step is a step of separating the mold from the cured film of the curable composition (A). In the planarizing film forming method, a substrate having irregularities with a height difference of about 10 to 1,000 nm is used as the substrate, and a mold having a flat surface is used as the mold, and a cured film having a surface following the flat surface of the mold is formed through the contacting step, the curing step, and the demolding step. In the disposing step, droplets of the curable composition (A) are densely disposed in the recessed portions of the substrate, and the curable composition (A) is sparsely disposed in the protruding portions of the substrate. The waiting step is performed after the disposing step, the contacting step is performed after the waiting step, the curing step is performed after the contacting step, and the demolding step is performed after the curing step.
[0219] [Production method] The method for manufacturing an article includes a forming step of forming a film of a curable composition on a substrate using the above-mentioned film forming method, a processing step of processing the substrate on which the film of the curable composition has been formed in the forming step, and a manufacturing step of manufacturing an article from the substrate processed in the processing step. As described above, the film forming method is a pattern forming method or a planarizing film forming method.
[0220] Furthermore, the cured film 108 having a pattern formed by the pattern forming method of the present invention is used as it is as at least a part of a constituent member of various articles. The cured film 108 having a pattern formed by the pattern forming method of the present invention is temporarily used as a mask for etching or ion implantation of the substrate 101 (or the substrate 101 having a layer to be processed, if the substrate 101 has such a layer). After etching or ion implantation is performed in the processing step of the substrate 101, the mask is removed. This allows various articles to be manufactured.
[0221] When the cured material in the recesses of the cured material pattern is removed by etching, the specific method is not particularly limited, and a known method, for example, dry etching, can be used. A known dry etching device can be used for dry etching. The source gas for dry etching is appropriately selected according to the elemental composition of the cured material to be etched. Specifically, halogen gases such as CF4, C2F6, C3F8, CCl2F2, CCl4, CBrF3, BCl3, PCl3, SF6, and Cl2 can be used as the source gas. In addition, gases containing oxygen atoms such as O2, CO, and CO2, inert gases such as He, N2, and Ar, and gases such as H2 and NH3 can also be used as the source gas. These gases can also be mixed and used as the source gas. In this case, in order to process the base substrate with a high yield, the photocured film is required to have a high dry etching resistance.
[0222] The article is an electric circuit element, an optical element, a MEMS, a recording element, a sensor, or a mold. Examples of the electric circuit element include volatile or non-volatile semiconductor memories such as DRAM, SRAM, flash memory, and MRAM, and semiconductor elements such as LSI, CCD, image sensor, and FPGA. Examples of the optical element include a microlens, a light guide, a waveguide, an anti-reflection film, a diffraction grating, a polarizing element, a color filter, a light-emitting element, a display, and a solar cell. Examples of the MEMS include a DMD, a microchannel, and an electromechanical conversion element. Examples of the recording element include an optical disk such as a CD or a DVD, a magnetic disk, a magneto-optical disk, and a magnetic head. Examples of the sensor include a magnetic sensor, an optical sensor, and a gyro sensor. Examples of the mold include a mold for imprinting.
[0223] Also, known photolithography processes such as imprint lithography and extreme ultraviolet exposure (EUV) can be performed on the planarization film formed by the planarization film forming method of the present invention. Also, a spin-on-glass (SOG) film and / or a silicon oxide layer can be laminated, and a curable composition can be applied thereon to perform a photolithography process. This allows devices such as semiconductor devices to be manufactured. Also, devices including such devices, such as electronic devices such as displays, cameras, and medical devices, can be formed. Examples of devices include, for example, LSI, system LSI, DRAM, SDRAM, RDRAM, D-RDRAM, and NAND flash.
[0224] [Example] To supplement the above-described embodiment, a more specific example will be described.
[0225] <Example 1> In Example 1, it is shown that by making α2 larger than α1 by adding a surfactant, the spreading of the droplet on the substrate can be controlled by the pinning effect, and the amount of spillover can be suppressed. Furthermore, it is shown that by making γ1 larger than γ2, the amount of spillover can be suppressed while still forming a liquid film due to the spreading of the droplet.
[0226] In Example 1, an experiment was conducted on droplet spreading using three types of compositions, as shown in Table 1 below. In Table 1, FS2000M1 (manufactured by CHANGZHOU FOREIGN) is the surfactant. Composition 1 is a composition that does not contain a surfactant, composition 2 is a composition to which 0.4 wt% of a surfactant is added by mass, and composition 3 is a composition to which 3% of a surfactant is added by mass.
[0227] [Table 1]
[0228] First, it is shown that α2 becomes larger than α1 by adding a surfactant. For the measurement of the contact angle, the amount of droplet was 1 μL, and an automatic static contact angle measuring device Dropmaster300 (manufactured by Kyowa Interface Science Co., Ltd.) was used. FIG. 11 is a diagram showing the results of measuring the contact angle with respect to the substrate for each of compositions 1, 2, and 3. In FIG. 11, the horizontal axis is time, and the vertical axis is contact angle, showing the change in contact angle of each composition over time. Referring to FIG. 11, it can be seen that at each time, the contact angle of composition 2 is larger than that of composition 1, the contact angle of composition 3 is larger than that of composition 2, and α2 is larger than α1. In FIG. 11, the contact angle of composition 2 10 seconds after the droplet of each composition is dropped is about 0.5° larger than that of composition 1.
[0229] Next, the change in surface tension with the addition of a surfactant is shown. The surface tension was measured by a plate method using a platinum plate using an automatic surface tensiometer DY-300 (manufactured by Kyowa Interface Science). FIG. 12 is a diagram showing the results of measuring the surface tension. In FIG. 12, the horizontal axis is the amount of surfactant added, and the horizontal axis is the value of the surface tension. Graph 901 is a graph showing the dependency of the surface tension of the curable composition in a state in which the solvent (d) has been removed on the amount of surfactant added, and graph 902 is a graph showing the value of the surface tension of the solvent. As described above, when γ1 is larger than γ2, the droplets spread quickly and form a liquid film. This is a region where the surface tension of graph 901 is larger than the surface tension of graph 902, and in FIG. 12, it is region 903. According to this, in composition 2, γ1 is larger than γ2, and in composition 3, γ1 is smaller than γ2.
[0230] Next, FIG. 13 shows the change in the radius of the droplet over time when a droplet of about 2 pL is dropped. An industrial material printer DMP-2850 (manufactured by Fujifilm) was used to photograph (measure) the droplet dropping and the spreading state of the droplet. In FIG. 13, the horizontal axis is time and the vertical axis is the radius of the droplet. Referring to FIG. 13, it can be seen that in composition 1, the droplet spreads over time, but in composition 2, the spreading of the droplet stops at an appropriate radius due to the pinning effect. It can also be seen that in composition 3, the droplet shrinks due to the pinning effect and Marangoni effect. In this way, it is possible to control the spreading of the droplet by exerting the pinning effect by adding a surfactant.
[0231] Next, the amount of overflow of the liquid film was measured using an industrial material printer DMP-2850 (manufactured by Fujifilm) when droplets of about 2 pL were arranged in an array of six rows at a pitch of 70 μm. The amount of overflow of the liquid film was defined as the length of the liquid film minus 70 × 6 μm. In FIG. 14, the horizontal axis is time, and the vertical axis is the amount of overflow. Regarding composition 3, due to excessive shrinkage, a substantially continuous liquid film could not be formed, and the purpose of the waiting step could not be achieved, so it was determined to be unsuitable. Typically, with composition 3, as shown in FIG. 15, droplets 1302 are isolated on substrate 1301. On the other hand, with composition 1 and composition 2, a substantially continuous liquid film can be formed, and typically, as shown in FIG. 16, droplets are bonded to each other on substrate 1201 to form liquid film 1202.
[0232] Regarding compositions 1 and 2 other than composition 3, which was judged to be unsuitable, referring to FIG. 14, it can be seen that in composition 1, the amount of protrusion is large and increases with time, whereas in composition 2, the amount of protrusion is small and has little dependency on time.
[0233] A summary of the experimental results for composition 1, composition 2, and composition 3 is shown in Fig. 17. Fig. 17 shows the amount of overflow after 600 seconds. Referring to Fig. 17, it can be seen that by making α2 larger than α1, as in the case of composition 1 to composition 2, it is possible to suppress the amount of overflow from 120 µm to 48 µm. It can also be seen that by making γ1 larger than γ2, as in the case of composition 3 to composition 2, it is possible to achieve compatibility with liquid film formation.
[0234] Thus, it was shown that by making α2 larger than α1, it is possible to suppress the amount of overflow. Also, it was shown that by making γ1 larger than γ2, it is possible to achieve compatibility with liquid film formation. As shown in Figure 11, it is preferable that the contact angle 10 seconds after the droplet is dropped is α2-α1>0.5°.
[0235] Next, a preferred Δγ defined by the following formula (3) will be described.
[0236] Δγ=γ1-γ2 Equation (3) Figure 18 shows the dependence of the maximum radius of a droplet on Δγ when a droplet of about 1 pL is dropped. Figure 18 shows the results of a numerical calculation obtained by solving the Navier-Stokes equations approximated as a thin film (lubrication theory) with a free surface. In Figure 18, the horizontal axis is Δγ [mN / m], and the vertical axis is Δr [μm]. Here, Δr is defined by the following equation (4).
[0237] Δr=r-r0 formula (4) In equation (4), r is the maximum radius of the droplet, and r0 is the maximum radius of the droplet when Δγ=0.
[0238] 18, if Δγ>0.1 mN / m, Δr>1 μm, and it is understood that the droplet spreads more than when Δγ=0, and furthermore, if Δγ>1 mN / m, Δr>10 μm, and the droplet spreads more significantly than when Δγ=0. Therefore, in order to see an effect on the maximum radius of the droplet, it is understood that Δγ>0.1 mN / m is preferable, and Δγ>1 mN / m is more preferable.
[0239] <Example 2> In Example 2, it is shown that by increasing β to more than 25° by adding a surfactant, it is possible to control the spreading of the droplets on the surface of the mold by the pinning effect, and to suppress the seepage height to the side wall of the mold. In Example 2, experiments were also conducted using the three compositions shown in Table 1.
[0240] First, it is shown that β (contact angle) increases with the addition of a surfactant. The contact angle was measured in the same manner as in Example 1. FIG. 19 is a diagram showing the results of measuring the contact angle with respect to the mold for each of composition 1, composition 2, and composition 3. In FIG. 19, the horizontal axis is time, and the vertical axis is contact angle, showing the change in contact angle with respect to the surface of the mold with respect to each composition over time. Referring to FIG. 19, it can be seen that at each time point after 1 second, the contact angle is larger for composition 2 than for composition 1, and the contact angle is larger for composition 3 than for composition 2, and β is increasing. In FIG. 19, the contact angle 10 seconds after the droplets of each composition are dropped is about 14° for composition 1, and about 31° for composition 2.
[0241] Next, the results of numerical calculation of the exudation height for different contact angles are shown in Figure 20. Figure 20 shows the results obtained by approximating the substrate and mold as rigid bodies and solving the Navier-Stokes equations approximated as thin films. In Figure 20, the horizontal axis is the contact angle and the vertical axis is the exudation height.
[0242] 20, it can be seen that the seepage height of composition 1 with a contact angle of about 14° is about 95 nm, and the seepage height of composition 2 with a contact angle of about 31° is about 70 nm. Therefore, it can be seen that it is possible to suppress the seepage height by selecting composition 2 instead of composition 1. Note that, as for composition 3, since it has a higher contact angle, it is possible to further suppress the seepage height, but it can be seen from Example 1 that composition 2, in which γ1 is larger than γ2, is necessary in order to be compatible with liquid film formation.
[0243] According to the abbreviations shown in Table 2, as shown in Table 3, curable compositions (A) were mixed so that the total of components (a), (b), (c) and (d) was 100% by weight, and curable compositions (A) were also mixed without using component (d). The viscosities of these curable compositions (A) at 23°C were measured, and the Si atom content and post-curing Tg of the curable compositions when component (d) was removed were calculated and measured by the above-mentioned method, and the results are shown in Table 4. In addition, in the component (d) shown in Table 3, PGEA is an abbreviation for propylene glycol monomethyl ether, and Gly is an abbreviation for glycerin.
[0244] [Table 2]
[0245] [Table 3]
[0246] [Table 4]
[0247] <Evaluation of inkjet ejection> The inkjet discharge was evaluated using a commercially available industrial material printer DMP-2850 (manufactured by Fujifilm). Cartridges were filled with the curable compositions of Examples 3 to 28 and Comparative Examples 1 and 2 shown in Table 3. The state of droplet discharge was observed with a built-in discharge observation camera, and the inkjet discharge was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: At ejection speeds (flight speeds) of 6 m / sec or more, no deviation (distortion) in the impact position was observed. AA: At ejection speeds of 6 m / sec or more, a very slight deviation in the impact position was observed that had no practical effect. A: At ejection speeds of 4 m / sec or more, a very slight deviation in the impact position was observed that had no practical effect. B: No discharge.
[0248] <Evaluation of overhang amount> The amount of overflow was evaluated using a commercially available industrial material printer DMP-2850 (manufactured by Fujifilm). The curable compositions of Examples 3 to 28 and Comparative Examples 1 and 2 shown in Table 3 were filled into cartridges. Droplets of about 2 pl were dropped and arranged in an array of 6 rows at a pitch of 70 μm. In all Examples and Comparative Examples, it was confirmed that the liquid film after 600 seconds had formed a substantially continuous liquid film, and the amount of overflow was measured. The amount of overflow of the liquid film was defined as the amount obtained by subtracting 70×6 μm from the length of the liquid film, and the amount of overflow was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: The amount of protrusion was 50 μm or less. AA: The amount of protrusion was 70 μm or less. A: The amount of protrusion was 100 μm or less. B: The amount of protrusion was greater than 100 μm.
[0249] <Evaluation of seepage amount> The amount of seepage was evaluated using a commercially available industrial material printer DMP-2850 (manufactured by Fujifilm). The curable compositions of Examples 3 to 28 and Comparative Examples 1 and 2 shown in Table 3 were filled into a cartridge at an amount of 1 pL. A pattern array was prepared by setting the X Width to 25.5 mm, the Y Height to 32.5 mm, and the Drop Spacing to 50 μm using the pattern editor software of DMP-2850. Then, droplets were dropped onto a silicon substrate, and a placement step, a waiting step, and a contact step were performed using a quartz blank mold. The placement step, the waiting step, and the contact step were performed under a carbon dioxide atmosphere, and the outer periphery of the plain mold after the steps was photographed at intervals of 500 μm to obtain a total of 232 images. All images were observed, and the amount of seepage was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: Seepage was observed in 1% or less of the images. AA: Seepage was observed in 3% or less of the images. A: Seepage was observed in less than 5% of the images. B: The number of images in which seepage was observed was more than 5% of the total.
[0250] <Drop Join Evaluation> Under conditions in which the thickness of the liquid film before the solvent (d) volatilizes is 80 nm, the curable compositions of Examples 3 to 28 and Comparative Examples 1 and 2 shown in Table 3 were discretely dropped (placed) on a silicon substrate. Then, the time until a substantially continuous liquid film was formed was measured, and the drop bonding was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: A substantially continuous liquid film was formed within less than 100 seconds. AA: A substantially continuous liquid film was formed within 100 seconds or more and less than 200 seconds. A: A substantially continuous liquid film was formed within a time period of 200 seconds or more and less than 300 seconds. B: No substantial continuous liquid film was formed even after 300 seconds.
[0251] <Evaluation of pattern collapse> A placement step, a waiting step, a contact step, a curing step, and a demolding step were carried out using a quartz mold in which a line-and-space (L / S) pattern with a depth of 50 nm and a width of 20 nm was formed over the entire area of the curable compositions of Examples 3 to 28 and Comparative Examples 1 and 2 shown in Table 3. The patterns obtained through these steps were observed, and the pattern collapse was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: Pattern collapse was observed in less than 0.5% of the pattern-formed region. AA: Pattern collapse was observed in less than 1% of the pattern-formed region. A: Pattern collapse was observed in less than 10% of the pattern formation area. B: Pattern collapse was observed in 10% or more of the pattern formation area.
[0252] <Evaluation of dry etching resistance> Cured films obtained from the curable compositions of Examples 3 to 22 and Comparative Examples 1 and 2 shown in Table 3 were exposed to oxygen plasma in a dry etching apparatus. Cured films obtained from the curable compositions of Examples 23 to 28 shown in Table 3 were exposed to CF4 plasma in a dry etching apparatus. Then, the weight change of the cured film remaining after the exposure was measured, and the dry etching resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) AAA: The weight of the remaining cured film was 46% or more before etching. AA: The weight of the remaining cured film was 42% or more of the weight before etching. A: The weight of the remaining cured film was 38% or more before etching. B: The weight of the remaining cured film was less than 38% of that before etching.
[0253] The evaluation results to date are shown in Table 5 below.
[0254] [Table 5]
[0255] It can be seen that when the viscosity of the curable composition at 23°C is 2 mPa·s or more and 60 mPa·s or less, inkjet discharge is good, and a viscosity of 5 mPa·s or more and 30 mPa·s or less is preferable, and a viscosity of 5 mPa·s or more and 15 mPa·s or less is even more preferable.
[0256] When the contact angle of the composition excluding the solvent (d) and the surfactant (c1) with respect to the substrate is α1 [°] and the contact angle of the composition excluding the solvent (d) with respect to the substrate is α2 [°], it is understood that the amount of overflow is good if α2 is larger than α1. It is also understood that it is preferable that α2-α1>0.5, and more preferably that α2-α1≧3.0.
[0257] It can be seen that the amount of seepage is good when the contact angle β [°] of the composition excluding the solvent (d) with quartz is β≧25°, preferably β≧30°, and more preferably β≧40°.
[0258] It can be seen that the drop bonding is good if γ1 is larger than γ2, where γ1 [mN / m] is the surface tension of the composition without the solvent (d) at 23° C., and γ2 [mN / m] is the surface tension of the solvent (d) at 23° C. It can also be seen that γ1-γ2≧1.0 is preferable, and γ1-γ2≧2.0 is even more preferable.
[0259] It can be seen that the pattern collapse occurs when the glass transition temperature of the curable composition after curing is preferably 70° C. or higher, more preferably 100° C. or higher, and even more preferably 130° C. or higher.
[0260] It is seen from Examples 3 to 22 and Comparative Examples 1 and 2 that the dry etching resistance is preferably such that the OP of the polymerizable compound (a) is 1.80 or more and 4.00 or less, more preferably such that the OP is 2.00 or more and 3.50 or less, and even more preferably such that the OP is 2.40 or more and 3.00 or less. It is also seen from Examples 3 to 28 that the dry etching resistance is preferably such that the Si content of the polymerizable compound (a) is 10% by weight or more, more preferably such that the Si content is 15% by weight or more, and even more preferably such that the Si content is 20% by weight or more.
[0261] The disclosure of the present specification includes the following curable compositions, film-forming methods, and methods for producing articles.
[0262] (Item 1) A curable composition comprising a polymerizable compound (a), a photopolymerization initiator (b), a solvent (d), and a surfactant (c1), The curable composition has a viscosity of 1.3 mPa s or more and 60 mPa s or less at 23° C. and 1 atmospheric pressure, The content of the solvent (d) relative to the entire curable composition is more than 5 volume % and not more than 95 volume %, The boiling point of the solvent (d) is less than 250° C. at 1 atmospheric pressure; a contact angle of a composition obtained by removing the solvent (d) and the surfactant (c1) from the curable composition to a substrate is defined as α1 [°], and a contact angle of a composition obtained by removing the solvent (d) from the curable composition to the substrate is defined as α2 [°], where α2 is larger than α1; A curable composition comprising:
[0263] (Item 2) 2. The curable composition according to item 1, wherein α2-α1>0.5[°].
[0264] (Item 3) A curable composition comprising a polymerizable compound (a), a photopolymerization initiator (b), a solvent (d), and a surfactant (c1), The curable composition has a viscosity of 1.3 mPa s or more and 60 mPa s or less at 23° C. and 1 atmospheric pressure, The content of the solvent (d) relative to the entire curable composition is more than 5 volume % and not more than 95 volume %, The boiling point of the solvent (d) is less than 250° C. at 1 atmospheric pressure; the contact angle β [°] of the composition obtained by removing the solvent (d) from the curable composition to a mold is 25° or more; A curable composition comprising:
[0265] (Item 4) 4. The curable composition according to any one of items 1 to 3, wherein, when a surface tension of a composition obtained by removing the solvent (d) from the curable composition at 23° C. and 1 atmospheric pressure is γ1 [mN / m], and a surface tension of the solvent (d) at 23° C. and 1 atmospheric pressure is γ2 [mN / m], γ1 is larger than γ2.
[0266] (Item 5) 5. The curable composition according to item 4, wherein γ1-γ2>0.1 [mN / m].
[0267] (Item 6) 5. The curable composition according to item 4, wherein γ1-γ2>1 [mN / m].
[0268] (Item 7) 7. The curable composition according to any one of items 1 to 6, wherein the surfactant (c1) contains a fluorine atom.
[0269] (Item 8) 7. The curable composition according to any one of items 1 to 6, wherein the surfactant (c1) contains a silicon atom.
[0270] (Item 9) 9. The curable composition according to any one of items 1 to 8, wherein a composition obtained by removing the solvent (d) from the curable composition has a viscosity of 30 mPa s or more and 10,000 mPa s or less at 23° C. and 1 atmospheric pressure.
[0271] (Item 10) The solvent (d) includes one or more solvents, and the boiling point of each of the one or more solvents at 1 atmospheric pressure is 100° C. or higher and lower than 250° C. The curable composition according to any one of items 1 to 9.
[0272] (Item 11) 11. The curable composition according to any one of items 1 to 10, wherein the solvent (d) contains a polymerizable compound having a boiling point of 100° C. or higher and lower than 250° C. at 1 atmospheric pressure.
[0273] (Item 12) 12. The curable composition according to any one of items 1 to 11, wherein the solvent (d) includes one or more solvents, and the boiling point of each of the one or more solvents at 1 atmospheric pressure is 100° C. or higher and lower than 200° C.
[0274] (Item 13) 13. The curable composition according to any one of items 1 to 12, wherein the content of the solvent (d) in the entire curable composition is 40% by volume or more and 85% by volume or less.
[0275] (Item 14) 14. The curable composition according to any one of items 1 to 13, wherein the ratio of the polyfunctional polymerizable compound in the polymerizable compound (a) is 20% by weight or more.
[0276] (Item 15) 15. The curable composition according to any one of items 1 to 14, wherein the polymerizable compound (a) includes one or more polymerizable compounds, and each of the one or more polymerizable compounds has a boiling point at 1 atmospheric pressure of 250° C. or higher.
[0277] (Item 16) 16. The curable composition according to any one of items 1 to 15, wherein the polymerizable compound (a) includes one or more polymerizable compounds, and each of the one or more polymerizable compounds has a molecular weight of 200 or more.
[0278] (Item 17) 17. The curable composition according to any one of items 1 to 16, wherein the polymerizable compound (a) includes a polymer having a polymerizable functional group.
[0279] (Item 18) 18. The curable composition according to any one of items 1 to 17, wherein the polymerizable compound (a) has a glass transition temperature of 70° C. or higher after curing.
[0280] (Item 19) 19. The curable composition according to any one of items 1 to 18, wherein the polymerizable compound (a) contains one or more polymerizable compounds, and each of the one or more polymerizable compounds has a vapor pressure of 0.001 mmHg or less at 80° C. and 1 atm.
[0281] (Item 20) 20. The curable composition according to any one of items 1 to 19, wherein the polymerizable compound (a) includes a compound (a-1) having an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure.
[0282] (Item 21) The polymerizable compound (a) contains one or more polymerizable compounds, the Ohnishi parameter (OP) of the polymerizable compound (a) is 1.80 or more and 4.00 or less, and is a mole fraction weighted average value of the N / (Nc-No) value of each molecule of the one or more polymerizable compounds, where N is the total number of atoms in the molecule, Nc is the number of carbon atoms in the molecule, and No is the number of oxygen atoms in the molecule; 21. The curable composition according to any one of items 1 to 20,
[0283] (Item 22) 22. The curable composition according to any one of items 1 to 21, wherein the polymerizable compound (a) includes a compound (a-2) containing a silicon atom.
[0284] (Item 23) 23. The curable composition according to item 22, wherein the compound (a-2) includes a polymerizable compound having a silsesquioxane skeleton or a cyclic siloxane compound.
[0285] (Item 24) 24. The curable composition according to any one of items 1 to 23, wherein a composition obtained by removing the solvent (d) from the curable composition contains 10% by weight or more of Si atoms.
[0286] (Item 25) 25. The curable composition according to any one of items 1 to 24, wherein the curable composition is a curable composition for inkjet printing.
[0287] (Item 26) The solubility coefficient of carbon dioxide in the curable composition is 0.5 kg / m 3 ·ATM or more 10kg / m 3 26. The curable composition according to any one of items 1 to 25, wherein the viscosity of the curable composition is 0.05 atm or less.
[0288] (Item 27) A film-forming method for forming a film of a curable composition in a space between a mold and a substrate, comprising the steps of: A disposing step of disposing a plurality of droplets of the curable composition according to any one of items 1 to 26 on the substrate in a discrete manner; a waiting step of waiting until the plurality of droplets combine with adjacent droplets to form a liquid film; a contacting step of contacting the mold with the liquid film after the waiting step; A film forming method comprising the steps of:
[0289] (Item 28) 28. The film forming method according to item 27, wherein in the waiting step, the process waits until the solvent contained in the liquid film evaporates and the content of the solvent becomes 10 volume % or less with respect to the entire liquid film.
[0290] (Item 29) 29. The film forming method according to item 27 or 28, wherein in the waiting step, the substrate is heated under conditions of 30° C. or higher and 200° C. or lower for 10 seconds or higher and 600 seconds or lower.
[0291] (Item 30) In the disposing step, droplets of the curable composition having a volume of 1.0 pL or more are deposited on the substrate at a density of 80 droplets / mm 2 30. The method for forming a film according to any one of items 27 to 29, wherein the particles are arranged at a density of at least 100 nm.
[0292] (Item 31) 31. The method for forming a film according to any one of items 27 to 30, wherein an average remaining liquid film thickness, which is a value obtained by dividing the volume of the curable composition remaining after the waiting step by the area of the film-forming region, is 20 nm or less.
[0293] (Item 32) The mold includes a pattern; In the contacting step, the pattern of the mold is brought into contact with the liquid film, The film forming method further includes a curing step of curing the liquid film after the contacting step to form a cured film having a pattern corresponding to the pattern of the mold. 32. The film forming method according to any one of items 27 to 31,
[0294] (Item 33) the mold includes a flat surface; In the contacting step, the flat surface of the mold is brought into contact with the liquid film, The film forming method further includes a curing step of curing the liquid film after the contact step to form a cured film having a surface conforming to the flat surface of the mold. 32. The film forming method according to any one of items 27 to 31,
[0295] (Item 34) 34. The film forming method according to any one of items 27 to 33, wherein in the disposing step, the plurality of droplets are discretely disposed on the substrate by using an inkjet method.
[0296] (Item 35) 35. The film forming method according to any one of items 27 to 34, wherein in the contact step, the gas filling the space between the mold and the substrate contains carbon dioxide at a molar ratio of 10% or more.
[0297] (Item 36) A forming step of forming a film of a curable composition on a substrate by using the film forming method according to any one of items 27 to 35; a processing step of processing the substrate on which the film is formed in the forming step; a manufacturing process for manufacturing an article from the substrate processed in the processing process; A method for producing an article, comprising the steps of:
[0298] The invention is not limited to the above-described embodiments, and various modifications and variations are possible without departing from the spirit and scope of the invention. Accordingly, the following claims are appended to apprise the public of the scope of the invention. [Explanation of symbols]
[0299] 101: Substrate 102: Droplet 103: Liquid film 104: Liquid film 105: Solvent 106: Mold 107: Irradiation light 108: Hardened film
Claims
1. A curable composition comprising a polymerizable compound (a), a photopolymerization initiator (b), a solvent (d), and a surfactant (c1), The curable composition has a viscosity of 1.3 mPa·s or more and 60 mPa·s or less at 23° C. and 1 atmosphere, The content of the solvent (d) relative to the entire curable composition is greater than 5 vol% and less than 95 vol%, The boiling point of the solvent (d) is less than 250° C. at 1 atmospheric pressure; a contact angle of a composition obtained by removing the solvent (d) and the surfactant (c1) from the curable composition to a substrate is defined as α1 [°], and a contact angle of a composition obtained by removing the solvent (d) from the curable composition to the substrate is defined as α2 [°], where α2 is larger than α1; A curable composition comprising:
2. The curable composition according to claim 1, characterized in that α2-α1>0.5[°].
3. A curable composition comprising a polymerizable compound (a), a photopolymerization initiator (b), a solvent (d), and a surfactant (c1), The curable composition has a viscosity of 1.3 mPa·s or more and 60 mPa·s or less at 23° C. and 1 atmosphere, The content of the solvent (d) relative to the entire curable composition is greater than 5 vol% and less than 95 vol%, The boiling point of the solvent (d) is less than 250° C. at 1 atmospheric pressure; the contact angle β [°] of the composition obtained by removing the solvent (d) from the curable composition to a mold is 25° or more; A curable composition comprising:
4. The curable composition according to claim 1 or 3, characterized in that, when the surface tension of a composition obtained by removing the solvent (d) from the curable composition at 23°C and 1 atmospheric pressure is γ1 [mN / m], and the surface tension of the solvent (d) at 23°C and 1 atmospheric pressure is γ2 [mN / m], γ1 is greater than γ2.
5. The curable composition according to claim 4, characterized in that γ1-γ2>0.1 [mN / m].
6. The curable composition according to claim 4, characterized in that γ1-γ2>1 [mN / m].
7. The curable composition according to claim 1 or 3, wherein the surfactant (c1) contains a fluorine atom.
8. The curable composition according to claim 1 or 3, wherein the surfactant (c1) contains a silicon atom.
9. 4. The curable composition according to claim 1, wherein a composition obtained by removing the solvent (d) from the curable composition has a viscosity of 30 mPa·s or more and 10,000 mPa·s or less at 23° C. and 1 atmospheric pressure.
10. The curable composition according to claim 1 or 3, characterized in that the solvent (d) contains one or more solvents, and each of the one or more solvents has a boiling point at 1 atmospheric pressure of 100°C or higher and lower than 250°C.
11. The curable composition according to claim 1 or 3, wherein the solvent (d) contains a polymerizable compound having a boiling point at 1 atmospheric pressure of 100° C. or higher and lower than 250° C.
12. The curable composition according to claim 1 or 3, characterized in that the solvent (d) contains one or more solvents, and each of the one or more solvents has a boiling point at 1 atmospheric pressure of 100°C or higher and lower than 200°C.
13. The curable composition according to claim 1 or 3, wherein a content of the solvent (d) relative to the entire curable composition is 40 vol % or more and 85 vol % or less.
14. 4. The curable composition according to claim 1, wherein the ratio of the polyfunctional polymerizable compound in the polymerizable compound (a) is 20% by weight or more.
15. 4. The curable composition according to claim 1, wherein the polymerizable compound (a) contains one or more types of polymerizable compounds, and each of the one or more types of polymerizable compounds has a boiling point at 1 atmospheric pressure of 250°C or higher.
16. 3. The curable composition according to claim 1, wherein the polymerizable compound (a) contains one or more types of polymerizable compounds, and each of the one or more types of polymerizable compounds has a molecular weight of 200 or more.
17. The curable composition according to claim 1 , wherein the polymerizable compound (a) comprises a polymer having a polymerizable functional group.
18. 4. The curable composition according to claim 1, wherein the polymerizable compound (a) has a glass transition temperature after curing of 70° C. or higher.
19. 4. The curable composition according to claim 1, wherein the polymerizable compound (a) contains one or more kinds of polymerizable compounds, and each of the one or more kinds of polymerizable compounds has a vapor pressure of 0.001 mmHg or less at 80° C. and 1 atmosphere.
20. The curable composition according to claim 1 or 3, wherein the polymerizable compound (a) includes a compound (a-1) having an aromatic structure, an aromatic heterocyclic structure, or an alicyclic structure.
21. The polymerizable compound (a) contains one or more polymerizable compounds, the Ohnishi parameter (OP) of the polymerizable compound (a) is 1.80 or more and 4.00 or less, and is a mole fraction weighted average value of the N / (Nc-No) value of each molecule of the one or more polymerizable compounds, where N is the total number of atoms in the molecule, Nc is the number of carbon atoms in the molecule, and No is the number of oxygen atoms in the molecule; The curable composition according to claim 1 or 3.
22. 4. The curable composition according to claim 1, wherein the polymerizable compound (a) comprises a compound (a-2) containing a silicon atom.
23. The curable composition according to claim 22, wherein the compound (a-2) includes a polymerizable compound having a silsesquioxane skeleton or a cyclic siloxane compound.
24. 4. The curable composition according to claim 1, wherein a composition remaining after removing the solvent (d) from the curable composition contains 10% by weight or more of Si atoms.
25. The curable composition according to claim 1 or 3, which is a curable composition for inkjet use.
26. The solubility coefficient of carbon dioxide in the curable composition is 0.5 kg / m 3 ・ATM or more 10kg / m 3 4. The curable composition according to claim 1, wherein the viscosity is equal to or less than 0.5 atm.
27. A film-forming method for forming a film of a curable composition in a space between a mold and a substrate, comprising the steps of: A disposing step of disposing a plurality of droplets of the curable composition according to claim 1 or 3 discretely on the substrate; a waiting step of waiting until the plurality of droplets combine with adjacent droplets to form a liquid film; a contacting step of contacting the mold with the liquid film after the waiting step; A film forming method comprising the steps of:
28. 28. The film forming method according to claim 27, wherein in the waiting step, waiting is performed until the solvent contained in the liquid film volatilizes and the content of the solvent becomes 10 volume % or less with respect to the entire liquid film.
29. 28. The film forming method according to claim 27, wherein in the waiting step, the substrate is heated at a temperature of 30° C. or more and 200° C. or less for a period of 10 seconds or more and 600 seconds or less.
30. In the disposing step, droplets of the curable composition having a volume of 1.0 pL or more are deposited on the substrate at a rate of 80 droplets / mm 2 28. The film forming method according to claim 27, wherein the particles are arranged at a density of at least 100 nm.
31. 28. The film forming method according to claim 27, wherein an average remaining liquid film thickness, which is a value obtained by dividing the volume of the curable composition remaining after the waiting step by the area of the film-forming region, is 20 nm or less.
32. The mold includes a pattern; In the contacting step, the pattern of the mold is brought into contact with the liquid film, The film forming method further includes a curing step of curing the liquid film after the contacting step to form a cured film having a pattern corresponding to the pattern of the mold. The film forming method according to claim 27 .
33. the mold includes a flat surface; In the contacting step, the flat surface of the mold is brought into contact with the liquid film, The film forming method further includes a curing step of curing the liquid film after the contact step to form a cured film having a surface conforming to the flat surface of the mold. The film forming method according to claim 27 .
34. 28. The film forming method according to claim 27, wherein in the disposing step, the plurality of droplets are discretely disposed on the substrate by using an inkjet method.
35. 28. The film forming method according to claim 27, wherein in the contact step, the gas filling the space between the mold and the substrate contains carbon dioxide at a molar ratio of 10% or more.
36. A forming step of forming a film of a curable composition on a substrate by using the film forming method according to claim 27; a processing step of processing the substrate on which the film is formed in the forming step; a manufacturing process for manufacturing an article from the substrate processed in the processing process; A method for producing an article, comprising:
Citation Information
Patent Citations
Curable composition, film forming method, and method for manufacturing article
JP2022188736A